Toner and method for producing toner
By using polar monomer unit block polymerization in the electrophotography system to form a crystalline resin toner and introducing multivalent metals to form a mesh crosslinking structure, the crystalline resin development under high temperature and high humidity environment is solved. The problem of stripes achieves excellent low-temperature fixing and charge retention.
Patent Information
- Application Number
- CN201910506998.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-04-10
- Filing Date
- 2019-06-12
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2039-06-12
AI Technical Summary
In the conventional electrophotographic system, although the crystalline resin has excellent low-temperature fixing and charge retention properties when used as the toner, it is easy to form development stripes in high temperature and high humidity environments, affecting image quality.
Using a crystalline resin toner containing a specific structure, a micro-phase separation state is formed by block polymerization of two or more polar monomer units, and a polyvalent metal is introduced into the toner particles to form a mesh crosslink. The structure is to improve elastic modulus and charge retention, and to suppress development stripes.
It realizes excellent low-temperature fixing and charge retention in high temperature and high humidity environments, while suppressing development stripes, and improving the stability and quality of image output.
Smart Images

Figure FDA0005098366860000011 
Figure FDA0005098366860000041 
Figure GDA0004684147890000051
Abstract
Description
Technical Field
[0001] The present invention relates to a toner suitable for an electrophotographic system, an electrostatic recording system, an electrostatic printing system, etc., and a method for producing the toner. Background Art
[0002] In recent years, as electrophotographic full-color copiers have become popular, additional performance improvements such as higher speed and higher image quality as well as energy saving performance and shortening of the recovery time from a sleep state are required.
[0003] Specifically, a toner capable of being fixed at a lower temperature to reduce power consumption during fixing is required to meet energy saving requirements. In addition, a toner having excellent charge retention that shows a small change in charge amount through a long dormant state is required as a toner capable of shortening the recovery time from the dormant state.
[0004] Therefore, JP-A-2014-199423 and JP-A-2014-130243 propose toners using crystalline resins as toners excellent in low-temperature fixability. JP-A-2012-247629 proposes toners using an antistatic composition as a crystal nucleating agent as toners excellent in charge retention. Summary of the invention
[0005] Since the toner described in JP-A-2014-199423 uses a crystalline resin with a sharp melting property, excellent low-temperature fixing is possible. However, since the crystalline resin is used as the main binder, the elastic modulus of the toner is lower than the elastic modulus of the toner using an amorphous resin. Therefore, when long-term image output is performed in a high temperature and high humidity environment, coarse particles as aggregates of the toner may be formed due to loads such as stirring by a developing device. Then, such coarse particles may be captured between the developing sleeve and the regulating blade, and since the portion where the coarse particles are captured is not developed, image defects (development streaks) may occur.
[0006] Meanwhile, in the toner described in JP-A-2014-130243, the excellent crystallinity of the crystalline resin having a low glass transition temperature is promoted and the hydrophobicity is high, thereby ensuring excellent charge retention. However, due to the same reasons as those associated with the toner described in JP-A-2014-199423, image defects (development streaks) may occur.
[0007] As described in JP-A-2014-199423 and JP-A-2014-130243, a crystalline resin has a melting point and therefore exhibits excellent low-temperature fixability. At the same time, a crystalline resin has a low glass transition temperature, which is an indicator of molecular mobility, and therefore, easily forms development streaks. Therefore, it has been proposed to promote the crystallinity of a binder resin by adding a crystal nucleating agent as described in JP-A-2012-247629, or to introduce an annealing step, etc., but the resulting effect on suppressing development streaks is negligible.
[0008] Therefore, it has been proposed to provide a toner having a core-shell structure and to use a resin having a high glass transition temperature as a shell material.
[0009] However, low temperature fixability is determined by the melting deformation start temperature of a very small part of the toner, and when a resin having a high glass transition temperature is used as a shell material, melting deformation of the toner is less likely to occur. As a result, excellent low temperature fixability may not be obtained in some cases.
[0010] As can be seen from the above, low temperature fixability and development streaks are in a trade-off relationship. Therefore, in order to overcome this trade-off relationship and show excellent low temperature fixability, it is urgent to develop a toner that can suppress development streaks and show excellent charge retention even in long-term image output under high temperature and high humidity environments.
[0011] The present invention has been made in view of the above problems. The present invention provides a toner which exhibits excellent low-temperature fixability and which can suppress development streaks and exhibit excellent charge retention even in long-term image output under high temperature and high humidity environments. The present invention also provides a method for producing such a toner.
[0012] In a first aspect, the present invention provides a toner comprising toner particles including a binder resin, wherein
[0013] The binder resin includes a polymer A,
[0014] Polymer A contains
[0015] a first monomer unit derived from a first polymerizable monomer, and
[0016] a second monomer unit derived from a second polymerizable monomer different from the first polymerizable monomer;
[0017] The first polymerizable monomer is at least one selected from the group consisting of (meth)acrylates having an alkyl group having 18 to 36 carbon atoms;
[0018] Based on the total moles of all monomer units in polymer A, the content of the first monomer unit in polymer A is 5.0 mol% to 60.0 mol%;
[0019] Based on the total moles of all monomer units in polymer A, the content of the second monomer unit in polymer A is 20.0 mol% to 95.0 mol%;
[0020] The SP value of the first monomer unit is determined by SP 11 (J / cm 3 ) 0.5 The SP value of the second monomer unit is represented by SP 21 (J / cm 3 ) 0.5 When , the following equations (1) and (2) are satisfied:
[0021] The polymer A includes a multivalent metal;
[0022] The multivalent metal is at least one selected from the group consisting of Mg, Ca, Al and Zn; and
[0023] The content of the polyvalent metal in the toner particles is 25 ppm to 500 ppm by mass.
[0024] 3.00≤(SP 21 -SP 11 )≤25.00 (1)
[0025] 21.00≤SP 21 (2)
[0026] In a second aspect, the present invention provides a toner comprising toner particles including a binder resin, wherein
[0027] The binder resin includes a polymer A,
[0028] Polymer A is a polymer of the composition comprising:
[0029] a first polymerizable monomer, and
[0030] a second polymerizable monomer different from the first polymerizable monomer;
[0031] The first polymerizable monomer is at least one selected from the group consisting of (meth)acrylates having an alkyl group having 18 to 36 carbon atoms;
[0032] The content of the first polymerizable monomer in the composition is 5.0 mol % to 60.0 mol % based on the total moles of all polymerizable monomers in the composition;
[0033] The content of the second polymerizable monomer in the composition is 20.0 mol % to 95.0 mol % based on the total moles of all polymerizable monomers in the composition;
[0034] The SP value of the first polymerizable monomer is determined by SP12 (J / cm 3 ) 0.5 The SP value of the second polymerizable monomer is represented by SP 22 (J / cm 3 ) 0.5 When , the following equations (4) and (5) are satisfied:
[0035] The polymer A includes a multivalent metal;
[0036] The multivalent metal is at least one selected from the group consisting of Mg, Ca, Al and Zn; and
[0037] The content of the polyvalent metal in the toner particles is 25 ppm to 500 ppm by mass.
[0038] 0.60≤(SP 22 -SP 12 )≤15.00 (4)
[0039] 18.30≤SP 22 (5)
[0040] Furthermore, the method for producing the toner of the present invention comprises:
[0041] a step of preparing a resin fine particle dispersion liquid including a binder resin;
[0042] a step of adding a flocculant to the resin fine particle dispersion to form aggregated particles; and
[0043] a step of heating and fusing the aggregated particles to obtain a dispersion liquid including toner particles, wherein
[0044] The binder resin includes a polymer A,
[0045] Polymer A is a polymer of the composition comprising:
[0046] a first polymerizable monomer, and
[0047] a second polymerizable monomer different from the first polymerizable monomer;
[0048] The first polymerizable monomer is at least one selected from the group consisting of (meth)acrylates having an alkyl group having 18 to 36 carbon atoms;
[0049] The content of the first polymerizable monomer in the composition is 5.0 mol % to 60.0 mol % based on the total moles of all polymerizable monomers in the composition;
[0050] The content of the second polymerizable monomer in the composition is 20.0 mol % to 95.0 mol % based on the total moles of all polymerizable monomers in the composition;
[0051] The SP value of the first polymerizable monomer is determined by SP 12 (J / cm 3 ) 0.5 The SP value of the second polymerizable monomer is represented by SP 22 (J / cm 3 ) 0.5 When , the following equations (4) and (5) are satisfied:
[0052] The polymer A includes a multivalent metal;
[0053] The multivalent metal is at least one selected from the group consisting of Mg, Ca, Al and Zn; and
[0054] The content of the polyvalent metal in the toner particles is 25 ppm to 500 ppm by mass.
[0055] 0.60≤(SP 22 -SP 12 )≤15.00 (4)
[0056] 18.30≤SP 22 (5)
[0057] According to the present invention, a toner showing excellent low-temperature fixability and suppressing development streaks and showing excellent charge retention even in long-term image output under high-temperature and high-humidity environments, and a method for producing the toner can be provided.
[0058] Further features of the present invention will become apparent from the following description of exemplary embodiments. DETAILED DESCRIPTION
[0059] In the present invention, unless otherwise specified, the expression "from XX to YY" or "XX to YY" expressing a numerical range means a numerical range including the lower limit and the upper limit as endpoints.
[0060] In the present invention, (meth)acrylate means acrylate and / or methacrylate.
[0061] In the present invention, the "monomer unit" refers to one carbon-carbon bond portion in the main chain of a polymer obtained by polymerizing a vinyl monomer as one unit. The vinyl monomer can be represented by the following formula (Z).
[0062]
[0063] (Among them, R Z1 represents a hydrogen atom or an alkyl group (preferably an alkyl group having 1 to 3 carbon atoms, more preferably a methyl group), and R Z2 represents an arbitrary substituent).
[0064] The crystalline resin refers to a resin that shows a clear endothermic peak in differential scanning calorimetry (DSC) measurement.
[0065] The inventors of the present invention have studied a toner which is excellent in low-temperature fixability and charge retention under a high-temperature and high-humidity environment and can suppress development streaks under a high-temperature and high-humidity environment. As a result, the inventors of the present invention have found that a desired toner can be obtained by appropriately crosslinking a crystalline resin having a specific structure. Specifically, it has been found that it is important to include a polyvalent metal in a crystalline resin obtained by block polymerization of two or more monomer units having polarities greatly different from each other.
[0066] That is, two or more monomer units with polarities greatly different from each other form a microphase separation state in the toner particles. Then, the polyvalent metal is oriented to a monomer unit phase with a larger polarity (hereinafter, also referred to as a "polar part"), and a crosslinking of the polyvalent metal and the polar part of the toner particles is formed. A monomer unit phase with a smaller polarity (hereinafter, also referred to as a "non-crosslinking part") that contributes to low-temperature fixability and charge retention and a crosslinking part of the polyvalent metal and the polar part of the toner particles that contributes to charge retention and suppressing development stripes can be formed in a network throughout the toner particles, and a domain matrix structure is formed in which a domain phase composed of the crosslinking part is dispersed in a matrix phase composed of the non-crosslinking part. Therefore, a toner with excellent low-temperature fixability, excellent charge retention and suppressing development stripes even under high temperature and high humidity conditions can be obtained. Since the molecular mobility of the binder resin is suppressed by crosslinking, the above effect is shown. That is, as a result of suppressing the molecular mobility of the binder resin, the elastic modulus of the toner is improved, and resistance to mechanical actions such as stirring of the developing device is shown, thereby suppressing development stripes. In addition, the formation of crosslinks suppresses charge transfer of the binder resin, thereby improving charge retention. At the same time, even if crosslinks are formed, the thermal responsiveness of the binder resin does not change, so that low-temperature fixability can be maintained.
[0067] In the toner according to the first aspect of the present invention, the binder resin includes a polymer A,
[0068] Polymer A contains
[0069] a first monomer unit derived from a first polymerizable monomer, and
[0070] a second monomer unit derived from a second polymerizable monomer different from the first polymerizable monomer;
[0071] The first polymerizable monomer is at least one selected from the group consisting of (meth)acrylates having an alkyl group having 18 to 36 carbon atoms;
[0072] Based on the total moles of all monomer units in polymer A, the content of the first monomer unit in polymer A is 5.0 mol% to 60.0 mol%;
[0073] Based on the total moles of all monomer units in polymer A, the content of the second monomer unit in polymer A is 20.0 mol% to 95.0 mol%;
[0074] The SP value of the first monomer unit is determined by SP 11 (J / cm 3 ) 0.5 The SP value of the second monomer unit is represented by SP 21 (J / cm 3 ) 0.5 When represented by , the following equations (1) and (2) are satisfied.
[0075] 3.00≤(SP 21 -SP 11 )≤25.00 (1)
[0076] 21.00≤SP 21 (2)
[0077] Furthermore, in the toner according to the second aspect of the present invention, the binder resin includes a polymer A,
[0078] Polymer A is a polymer of the composition comprising:
[0079] a first polymerizable monomer, and
[0080] a second polymerizable monomer different from the first polymerizable monomer;
[0081] The first polymerizable monomer is at least one selected from the group consisting of (meth)acrylates having an alkyl group having 18 to 36 carbon atoms;
[0082] The content of the first polymerizable monomer in the composition is 5.0 mol % to 60.0 mol % based on the total moles of all polymerizable monomers in the composition;
[0083] The content of the second polymerizable monomer in the composition is 20.0 mol % to 95.0 mol % based on the total moles of all polymerizable monomers in the composition;
[0084] The SP value of the first polymerizable monomer is determined by SP 12 (J / cm 3 ) 0.5 The SP value of the second polymerizable monomer is represented by SP 22 (J / cm 3 ) 0.5 When represented by , the following equations (4) and (5) are satisfied.
[0085] 0.60≤(SP 22 -SP 12 )≤15.00 (4)
[0086] 18.30≤SP 22 (5)
[0087] Here, the SP value is an abbreviation of a solubility parameter, and is a value used as an indicator of solubility. The calculation method thereof will be described below.
[0088] In the present invention, the binder resin includes a polymer A. The polymer A is a polymer of a composition including a first polymerizable monomer and a second polymerizable monomer different from the first polymerizable monomer. In addition, the polymer A has a first monomer unit derived from the first polymerizable monomer and a second monomer unit derived from the second polymerizable monomer different from the first polymerizable monomer.
[0089] The first polymerizable monomer is at least one selected from the group consisting of (meth)acrylates having an alkyl group having 18 to 36 carbon atoms. The first monomer unit is derived from the first polymerizable monomer.
[0090] Since the above-mentioned (meth)acrylate has a long alkyl group, it can impart crystallinity to the binder resin. As a result, the toner exhibits sharp melting properties and shows excellent low-temperature fixability. In addition, since the (meth)acrylate is highly hydrophobic, its hygroscopicity under high temperature and high humidity environments is low, which contributes to excellent charge retention.
[0091] Meanwhile, when the (meth)acrylate has an alkyl group containing less than 18 carbon atoms, the resulting polymer A has low hydrophobicity and high hygroscopicity under high temperature and high humidity environments due to the short alkyl chain, which results in poor charge retention. In addition, when the (meth)acrylate has an alkyl group containing more than 37 carbon atoms, the (meth)acrylate has a long-chain alkyl group, so its melting point is high and low-temperature fixability is poor.
[0092] The (meth)acrylate having an alkyl group having 18 to 36 carbon atoms can be exemplified by (meth)acrylate having a straight-chain alkyl group having 18 to 36 carbon atoms [octadecyl (meth)acrylate, nonadecyl (meth)acrylate, eicosyl (meth)acrylate, heneicosyl (meth)acrylate, behenyl (meth)acrylate, tetracosyl (meth)acrylate, hexacosyl (meth)acrylate, octadecyl (meth)acrylate, triacontyl (meth)acrylate, tridodecyl (meth)acrylate, etc.] and (meth)acrylate having a branched alkyl group having 18 to 36 carbon atoms [2-decyltetradecyl (meth)acrylate, etc.].
[0093] Among them, from the viewpoint of low-temperature fixing property, at least one selected from the group consisting of (meth)acrylates having a linear alkyl group having 18 to 36 carbon atoms is preferred, more preferably at least one selected from the group consisting of (meth)acrylates having a linear alkyl group having 18 to 30 carbon atoms, and even more preferably at least one of linear octadecyl (meth)acrylate and behenyl (meth)acrylate.
[0094] The first polymerizable monomer may be used alone or in combination of two or more thereof.
[0095] The second polymerizable monomer is a polymerizable monomer different from the first polymerizable monomer and satisfies formulas (1) and (2), or formulas (4) and (5). In addition, the second monomer unit is derived from the second polymerizable monomer. The second polymerizable monomer can be used alone or in combination of two or more thereof.
[0096] The second polymerizable monomer preferably has an ethylenically unsaturated bond, and more preferably has one ethylenically unsaturated bond.
[0097] The second polymerizable monomer is preferably at least one selected from the group consisting of compounds represented by the following formulae (A) and (B).
[0098]
[0099] (wherein X represents a single bond or an alkylene group having 1 to 6 carbon atoms,
[0100] R 1 for
[0101] Nitrile group (-C≡N),
[0102] Amino(-C(=O)NHR 10 (R 10 is a hydrogen atom or an alkyl group having 1 to 4 carbon atoms),
[0103] Hydroxyl,
[0104] -COOR 11 (R 11 is an alkyl group having 1 to 6 carbon atoms (preferably 1 to 4 carbon atoms) or a hydroxyalkyl group having 1 to 6 carbon atoms (preferably 1 to 4 carbon atoms),
[0105] Carbamate group (-NHCOOR 12 (R 12 is an alkyl group having 1 to 4 carbon atoms),
[0106] Urea (-NH-C(=O)-N(R 13 ) 2 (R 13independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms (preferably 1 to 4 carbon atoms),
[0107] -COO(CH 2 ) 2 NHCOOR 14 (R 14 is an alkyl group having 1 to 4 carbon atoms), or
[0108] -COO(CH 2 ) 2 -NH-C(=O)-N(R 15 ) 2 (R 15 independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms (preferably 1 to 4 carbon atoms).
[0109] Preferred R 1 for
[0110] Nitrile group (-C≡N),
[0111] Amino(-C(=O)NHR 10 (R 10 is a hydrogen atom or an alkyl group having 1 to 4 carbon atoms),
[0112] Hydroxyl,
[0113] -COOR 11 (R 11 is an alkyl group having 1 to 6 carbon atoms (preferably 1 to 4 carbon atoms) or a hydroxyalkyl group having 1 to 6 carbon atoms (preferably 1 to 4 carbon atoms),
[0114] Urea (-NH-C(=O)-N(R 13 ) 2 (R 13 independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms (preferably 1 to 4 carbon atoms),
[0115] -COO(CH 2 ) 2 NHCOOR 14 (R 14 is an alkyl group having 1 to 4 carbon atoms), or
[0116] -COO(CH 2 ) 2 -NH-C(=O)-N(R 15 ) 2 (R 15 independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms (preferably 1 to 4 carbon atoms).
[0117] R 2 is an alkyl group having 1 to 4 carbon atoms, and R 3 are each independently a hydrogen atom or a methyl group).
[0118] As a result of using at least one selected from the group consisting of compounds represented by the above-mentioned formulas (A) and (B) as the second polymerizable monomer, the second monomer unit becomes particularly polar, and a microphase separation state can be advantageously formed in the toner particles. In addition, the polyvalent metal can be advantageously oriented to the polar portion, and a network crosslinked portion can be advantageously formed. In addition, in the case where the polyvalent metal is crosslinked with a monomer unit of at least one compound derived from the group consisting of compounds represented by the free formulas (A) and (B), the bond between the monomer unit and the polyvalent metal is less strong than the bond obtained by crosslinking the following polyvalent metal with a polar portion having a carboxyl group. Therefore, development streaks can be suppressed without impairing low-temperature fixability.
[0119] In addition, since the compound including at least one of a nitrile group and an acylamino group is nonionic and highly polar, a more suitable crosslink can be formed, and such a compound is more preferably used as the second polymerizable monomer. In addition, since the compound including at least one of a nitrile group and an acylamino group is nonionic, the compound has high hydrophobicity and low hygroscopicity under high temperature and high humidity. Therefore, such a compound is also preferred because excellent charge retention can be shown.
[0120] Furthermore, specifically, among the polymerizable monomers listed below, for example, a polymerizable monomer satisfying formulae (1) and (2) or formulae (4) and (5) may be used as the second polymerizable monomer.
[0121] Monomers having a nitrile group, such as acrylonitrile and methacrylonitrile.
[0122] Examples of the monomer having a hydroxyl group include 2-hydroxyethyl (meth)acrylate and 2-hydroxypropyl (meth)acrylate.
[0123] The monomer having an acylamino group, for example, acrylamide and a monomer obtained by reacting an amine having 1 to 30 carbon atoms with a carboxylic acid having 2 to 30 carbon atoms and an ethylenically unsaturated bond such as acrylic acid and methacrylic acid by a known method.
[0124] The monomer having a carbamate group is prepared by, for example, reacting an alcohol having 2 to 22 carbon atoms and an ethylenically unsaturated bond (2-hydroxyethyl methacrylate, vinyl alcohol, etc.) with an isocyanate having 1 to 30 carbon atoms [monoisocyanate compounds (benzenesulfonyl isocyanate, p-toluenesulfonyl isocyanate, phenyl isocyanate, p-chlorophenyl isocyanate, butyl isocyanate, hexyl isocyanate, tert-butyl isocyanate, cyclohexyl isocyanate, octyl isocyanate, isocyanate] cyanate, 2-ethylhexyl isocyanate, dodecyl isocyanate, adamantyl isocyanate, 2,6-dimethylphenyl isocyanate, 3,5-dimethylphenyl isocyanate, 2,6-dipropylphenyl isocyanate, etc.), aliphatic diisocyanate compounds (trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, pentamethylene diisocyanate, 1,2-propylene diisocyanate, 1,3-butylene diisocyanate, dodecyl isocyanate, methylene diisocyanate, 2,4,4-trimethylhexamethylene diisocyanate, etc.), alicyclic diisocyanate compounds (1,3-cyclopentene diisocyanate, 1,3-cyclohexane diisocyanate, 1,4-cyclohexane diisocyanate, isophorone diisocyanate, hydrogenated diphenylmethane diisocyanate, hydrogenated xylylene diisocyanate, hydrogenated toluene diisocyanate, hydrogenated tetramethylxylylene diisocyanate, etc.), and aromatic diisocyanates. ester compounds (phenylene diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 2,2'-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate, 4,4'-toluidine diisocyanate, 4,4'-diphenyl ether diisocyanate, 4,4'-diphenyl diisocyanate, 1,5-naphthalene diisocyanate, xylylene diisocyanate, etc.)] obtained by a known method, and
[0125] A monomer obtained by reacting an alcohol having 1 to 26 carbon atoms (methanol, ethanol, propanol, isopropanol, butanol, tert-butanol, amyl alcohol, heptanol, octanol, 2-ethylhexanol, nonyl decanol, undecanol, lauryl alcohol, dodecanol, tetradecanol, pentadecyl alcohol, hexadecanol, heptadecanol, octadecyl alcohol, isostearyl alcohol, elaidoyl alcohol, oleyl alcohol, linoleyl alcohol, linoleyl alcohol, nonadecanol, heneicosyl alcohol, behenyl alcohol, docosyl alcohol, etc.) with an isocyanate having 2 to 30 carbon atoms and an ethylenically unsaturated bond [2-isocyanatoethyl (meth)acrylate, 2-(0-[1'-methylpropyleneamino]carboxyamino)ethyl (meth)acrylate, 2-[(3,5-dimethylpyrazolyl)carbonylamino]ethyl (meth)acrylate, 1,1-(bis(meth)acryloyloxymethyl)ethyl isocyanate, etc.] by a well-known method.
[0126] Monomer having a urea group: for example, a monomer obtained by reacting an amine having 3 to 22 carbon atoms [primary amine (n-butylamine, tert-butylamine, propylamine, isopropylamine, etc.), secondary amine (di-n-ethylamine, di-n-propylamine, di-n-butylamine, etc.), aniline, cycloxylamine, etc.] with an isocyanate having 2 to 30 carbon atoms and an ethylenically unsaturated bond by a known method.
[0127] The monomer having a carboxyl group is, for example, methacrylic acid, acrylic acid, and 2-carboxyethyl (meth)acrylate.
[0128] Among them, monomers having a nitrile group, an acylamino group, a carbamate group, a hydroxyl group or a urea group are preferably used, and more preferably, monomers having at least one functional group selected from the group consisting of a nitrile group, an acylamino group, a carbamate group, a hydroxyl group and a urea group and an ethylenically unsaturated bond are used.
[0129] In addition, vinyl esters such as vinyl acetate, vinyl propionate, vinyl butyrate, vinyl caproate, vinyl octanoate, vinyl decanoate, vinyl decanoate, vinyl laurate, vinyl myristate, vinyl palmitate, vinyl stearate, vinyl pivalate and vinyl octanoate are preferably used as the second polymerizable monomer. Among them, since vinyl esters are non-conjugated monomers, they are easy to maintain suitable reactivity with the first polymerizable monomer and can increase the crystallinity of the polymer, so low-temperature fixability and suppression of development streaks can be achieved at the same time.
[0130] The content of the first monomer unit in polymer A is 5.0 mol% to 60.0 mol% based on the total moles of all monomer units in polymer A. The content of the second monomer unit in polymer A is 20.0 mol% to 95.0 mol% based on the total moles of all monomer units in polymer A. In addition, the content of the first polymerizable monomer in the composition constituting polymer A is 5.0 mol% to 60.0 mol% based on the total moles of all polymerizable monomers in the composition, and the content of the second polymerizable monomer in the composition is 20.0% to 95.0 mol% based on the total moles of all polymerizable monomers in the composition.
[0131] When the content of the first monomer unit and the content of the first polymerizable monomer are within the above range, the toner exhibits sharp melting properties due to the crystallinity of the binder resin and exhibits excellent low-temperature fixability. In addition, when the content of the second monomer unit and the content of the second polymerizable monomer are within the above range, the content of the second monomer unit or the second polymerizable monomer that can form a crosslink with a polyvalent metal is suitable, and a network crosslinking portion can be formed in the entire toner particle. Therefore, it is possible to suppress molecular mobility and exhibit excellent charge retention while suppressing development streaks.
[0132] The content of the first monomer unit and the content of the first polymerizable monomer are preferably 10.0 mol % to 60.0 mol %, more preferably 20.0 mol % to 40.0 mol %.
[0133] Meanwhile, when the content of the first monomer unit or the content of the first polymerizable monomer is less than 5.0 mol%, the proportion of the non-crosslinked portion having crystallinity is small, and thus the low temperature fixability and charge retention are poor. In addition, when the content of the first monomer unit or the content of the first polymerizable monomer is greater than 60.0 mol%, the proportion of the crosslinked portion between the polar portion and the polyvalent metal described below is small, and thus the effect of suppressing development streaks is poor.
[0134] In addition, when the polymer A has a monomer unit derived from a (meth) acrylic acid ester having two or more alkyl groups having 18 to 36 carbon atoms, the content of the first monomer unit represents a molar ratio as the total thereof. Likewise, when the composition for the polymer A includes a (meth) acrylic acid ester having two or more alkyl groups having 18 to 36 carbon atoms, the content of the first polymerizable monomer represents a molar ratio as the total thereof.
[0135] In addition, when the content of the second monomer unit in polymer A is less than 20.0 mol% based on the total molar number of all monomer units in polymer A, the content of the monomer unit forming a crosslink is small, so the effect of suppressing development streaks and charge retention are poor. In addition, when the content of the second monomer unit in polymer A is greater than 95.0 mol% based on the total molar number of all monomer units in polymer A, the content of the monomer unit to be crystallized is small, so the low-temperature fixability is poor.
[0136] In addition, from the viewpoints of low-temperature fixability, suppression of development streaks, and charge retention, the content of the second monomer unit in the polymer A is preferably 40.0 mol% to 95.0 mol% relative to the total moles of all monomer units in the polymer A because a non-crosslinked portion having a sharp melting property and a crosslinked portion suppressing a decrease in the elastic modulus of the toner can be achieved. For the same reason, the content of the second polymerizable monomer in the composition is preferably 40.0 mol% to 95.0 mol%, more preferably 40.0 mol% to 70.0 mol%, relative to the total moles of all monomer units in the composition.
[0137] When two or more monomer units derived from the second polymerizable monomer satisfying formula (1) are present in polymer A, the ratio of the second monomer units is expressed as a molar ratio of their total. In addition, when the composition for polymer A includes two or more second polymerizable monomers, the content of the second polymerizable monomers is also expressed as a molar ratio of their total.
[0138] In polymer A, the SP value of the first monomer unit is given by SP11 (J / cm 3 ) 0.5 The SP value of the second monomer unit is represented by SP 21 (J / cm 3 ) 0.5 When represented by , the following equations (1) and (2) are satisfied.
[0139] 3.00≤(SP 21 -SP 11 )≤25.00 (1)
[0140] 21.00≤SP 21 (2)
[0141] In the polymer A in the toner according to the second aspect of the present invention, the SP value of the first polymerizable monomer is determined by SP 12 (J / cm 3 ) 0.5 The SP value of the second polymerizable monomer is represented by SP 22 (J / cm 3 ) 0.5 When represented by , the following equations (4) and (5) are satisfied.
[0142] 0.60≤(SP 22 -SP 12 )≤15.00 (4)
[0143] 18.30≤SP 22 (5)
[0144] When formula (1) and (2) or formula (4) and (5) are satisfied, the second monomer unit becomes highly polar, and a polarity difference occurs between the first and second monomer units. Due to this polarity difference, a microphase separation state can be formed in the toner. Then, the polyvalent metal can be oriented as a high-polarity monomer unit portion to form a network crosslink. As a result, the non-crosslinked portion that contributes to low-temperature fixability and charge retention and the crosslinked portion that contributes to suppressing development streaks and charge retention can exist in the form of a domain matrix. Therefore, a toner having excellent low-temperature fixability and charge retention and suppressing development streaks can be obtained.
[0145] Although the unit of SP value in the present invention is (J / m 3 ) 0.5 , but can be passed through 1(cal / cm 3 ) 0.5 =2.045×10 3 (J / m 3 ) 0.5 Carry out (cal / cm 3 ) 0.5 Conversion of units.
[0146] It is presumed that the following mechanism makes it possible to obtain excellent low-temperature fixability and charge retention and suppress development streaks by satisfying the formulae (1) and (2) or the formulae (4) and (5).
[0147] The first monomer unit is introduced into polymer A, and the first monomer unit aggregates to show crystallinity. Generally, since the crystallization of the first monomer unit is suppressed when other monomer units are introduced, it is impossible for the polymer to show crystallinity. This tendency becomes significant when multiple types of monomer units are randomly bonded to each other in one polymer molecule.
[0148] At the same time, it is conceivable that in the present invention, as a result of using the first polymerizable monomer and the second polymerizable monomer so that the content of the first monomer unit and the second monomer unit is within the range of formula (1) and (2), the first polymerizable monomer and the second polymerizable monomer can be continuously bonded to a certain extent during polymerization, rather than randomly bonded. For this reason, it is conceivable that a block of the first monomer unit aggregation is formed, and polymer A becomes a block copolymer, and even if other monomer units are introduced, crystallinity can be improved, and the melting point can be maintained. That is, preferably polymer A has a crystalline part including a first monomer unit derived from the first polymerizable monomer. In addition, preferably polymer A has an amorphous part including a second monomer unit derived from the second polymerizable monomer.
[0149] At the same time, when the SP value of the monomer unit is 11 and SP 21 for
[0150] (SP 21 -SP 11 )<3.00,
[0151] This means that the polarity difference between the monomer units is too small, a microphase separation state cannot be formed in the toner, and the effect of suppressing development streaks and charge retention are poor. 21 -SP 11 ), this means that the polarity difference between the monomer units is too large, the polymer A does not have a structure similar to a block copolymer, composition diffusion occurs between toner particles, and the low-temperature fixability, the effect of suppressing development streaks, and the charge retention are poor.
[0152] In addition, when the SP value of the second monomer unit is 21 for
[0153] SP 21 <21.00 hours,
[0154] The polarity of the second monomer unit is low, and no crosslinking is formed between the polar portion and the polyvalent metal, so the effect of suppressing development streaks and charge retention are poor.
[0155] SP 21 -SP 11 The lower limit of is preferably 4.00 or more, more preferably 5.00 or more. The upper limit is preferably 20.00 or less, more preferably 15.00 or less. 21 Above 22.00.
[0156] In the toner according to the second aspect, when the SP value of the polymerizable monomer is 12 and SP 22 (SP 22 -SP 12 )<0.60, this means that the polarity difference between the polymerizable monomers is too small, a microphase separation state cannot be formed in the toner, and the effect of suppressing development streaks and charge retention are poor. In addition, when 15.00<(SP 22 -SP 12 ), this means that the difference in polarity between the polymerizable monomers is too large, the polymer A does not have a structure similar to the block copolymer, composition diffusion occurs between toner particles, and the low-temperature fixability, the effect of suppressing development streaks, and the charge retention are poor.
[0157] In addition, when the SP value of the second polymerizable monomer is 22 For SP 22 When <18.30, the polarity of the second polymerizable monomer is low, and no crosslinking is formed between the polar portion and the polyvalent metal, so the effect of suppressing development streaks and charge retention are poor.
[0158] SP 22 -SP 12 The lower limit of is preferably 2.00 or more, more preferably 3.00 or more. The upper limit is preferably 10.00 or less, more preferably 7.00 or less. 22 It is 25.00 or more, and more preferably 29.00 or more.
[0159] In the present invention, when there are multiple types of monomer units satisfying the requirements of the first monomer unit in the polymer A, it is assumed that SP in formula (1) 11 The value is a value obtained by weighted average of the SP values of each monomer unit. For example, when the SP value is contained in A mol% based on the molar number of all monomer units that meet the requirements of the first monomer unit, 111 The monomer unit A of the first monomer unit, and the molar number of all monomer units satisfying the requirements of the first monomer unit is (100-A) mol% including the SP value SP 112 When the monomer unit B is11 )for
[0160] SP 11 =(SP 111 ×A+SP 112 ×(100-A)) / 100.
[0161] The same calculation is performed when there are three or more monomer units that meet the requirements of the first monomer unit. 12 The average value calculated from the molar ratio of each first polymerizable monomer is similarly indicated.
[0162] Meanwhile, the monomer unit derived from the second polymerizable monomer corresponds to a monomer unit having a relative SP calculated by the above method. 11 SP that satisfies formula (1) 21 Similarly, the second polymerizable monomer corresponds to the monomer having a SP calculated by the above method. 12 SP that satisfies formula (4) 22 of all polymerizable monomers.
[0163] That is, when the second polymerizable monomer is two or more polymerizable monomers, SP 21 represents the SP value of the monomer unit derived from each polymerizable monomer, and SP 21 -SP 11 is determined relative to the monomer units derived from each second polymerizable monomer. Similarly, SP 22 Indicates the SP value of each polymerizable monomer, SP 22 -SP 12 It is determined with respect to each second polymerizable monomer.
[0164] <Multivalent Metals>
[0165] The polymer A includes a polyvalent metal, and the polyvalent metal is at least one selected from the group consisting of Mg, Ca, Al and Zn. By including such a polyvalent metal, the polyvalent metal can be oriented to the polar part to form a network crosslink that helps to suppress development streaks. As a result, a toner having an excellent effect of suppressing development streaks can be obtained.
[0166] Meanwhile, when the polyvalent metal does not include at least one selected from the group consisting of Mg, Ca, Al and Zn, or when a polyvalent metal having a large atomic weight such as Sr or Ba is selected, the number of crosslinking points is reduced relative to the amount of the added polyvalent metal, and the crosslinking forming effect is reduced. As a result, the effect of suppressing development streaks and charge retention are poor.
[0167] In addition, the content of the polyvalent metal in the toner particles is 25 ppm to 500 ppm by mass. When the content of the polyvalent metal in the toner particles is within the above range, the crosslinking portion of the second monomer unit and the polyvalent metal becomes appropriate, and an appropriate crosslinking portion that does not impair low-temperature fixability and charge retention while showing an effect of suppressing development streaks can be formed.
[0168] Meanwhile, when the content of the polyvalent metal in the toner particles is less than 25 ppm, the number of crosslinking points between the polar part and the polyvalent metal is too small, and the effect of suppressing development streaks and charge retention are poor. In the case where the content of the polyvalent metal in the toner particles is greater than 500 ppm, low-temperature fixability is poor. In addition, since the amount of the monovalent metal described later is relatively reduced, the crosslinking with the polyvalent metal dominates the crosslinking of the polar part, and since the number of crosslinking points is reduced, the effect of suppressing development streaks and charge retention are poor.
[0169] The content of the polyvalent metal in the toner particles is preferably from 300 ppm to 400 ppm.
[0170] Furthermore, it is preferred that the amount of the polyvalent metal in the toner particles and the content of the second monomer unit in the polymer A satisfy the following formula (3).
[0171] (Content of polyvalent metal in toner particles) / (Content of second monomer unit in polymer A) ≥ 0.5 (ppm / mol%) (3)
[0172] In the toner according to the second aspect, it is preferred that the amount of the polyvalent metal in the toner particles and the content of the second polymerizable monomer in the composition satisfy the following formula (6).
[0173] (Content of polyvalent metal in toner particles) / (Content of second polymerizable monomer in composition)≥0.5 (ppm / mol%) (6)
[0174] As a result of satisfying the formula (3) or the formula (6), the ratio of the polyvalent metal and the polar part falls within the range most suitable for crosslink formation, and the effect of suppressing development streaks and excellent charge retainability are obtained.
[0175] (Content of polyvalent metal in toner particles) / (Content of second monomer unit in polymer A) or (Content of polyvalent metal in toner particles) / (Content of second polymerizable monomer in composition) is preferably from 0.6 ppm / mol% to 1.0 ppm / mol%.
[0176] Furthermore, in the concentration distribution of the polyvalent metal in the cross section of the toner particle, the polyvalent metal concentration in the region from the toner particle surface to a depth of 0.4 μm (hereinafter also referred to as "toner particle surface layer") is preferably lower than the polyvalent metal concentration in the region deeper than 0.4 μm from the toner particle surface (hereinafter also referred to as "toner particle interior"). Specifically, it is preferred to satisfy the following formula (7), and it is more preferred to satisfy the following formula (8).
[0177] (Polyvalent metal concentration in the surface layer of toner particles) / (Polyvalent metal concentration inside toner particles) < 1 (7)
[0178] (Polyvalent metal concentration in the surface layer of the toner particle) / (Polyvalent metal concentration inside the toner particle) ≤ 0.5 (8)
[0179] When the polyvalent metal concentration in the surface layer of the toner particles is lower than that in the interior of the toner particles, the number of crosslinked portions between the polar portion and the polyvalent metal in the toner particles increases, and an excellent effect of suppressing development streaks is obtained. In addition, since the number of non-crosslinked segments contributing to crystallinity in the surface layer of the toner particles increases, excellent low-temperature fixability is exhibited.
[0180] The concentration distribution of the polyvalent metal in the toner particles can be controlled by the metal removal step described below. The concentration distribution of the polyvalent metal in the toner particles is determined by mapping image analysis of the toner particle cross section described below using an energy dispersive X-ray spectrometer (EDX) of a scanning electron microscope (SEM).
[0181] The polymer A preferably includes a monovalent metal, and the monovalent metal is preferably at least one selected from the group consisting of Na, Li and K. By including such a monovalent metal, the polar part in the polymer A can form not only a crosslink between the polar part and the polyvalent metal, but also a crosslinking part between the polar part and the monovalent metal. Therefore, the toner has an excellent effect of suppressing development streaks and low-temperature fixability.
[0182] The amount of the monovalent metal is preferably 50% by mass to 90% by mass based on the total amount of the polyvalent metal and the amount of the monovalent metal. When the amount of the monovalent metal is within the above range, a domain phase consisting of a crosslinked portion of a polar portion and a polyvalent metal and a domain phase consisting of a crosslinked portion of a polar portion and a monovalent metal are more appropriately formed in the toner particles, and a suitable domain matrix structure can be formed without impairing low-temperature fixability, while exhibiting an effect of suppressing development streaks and charge retention.
[0183] The amount of the monovalent metal is preferably 60% by mass to 90% by mass based on the total of the amount of the polyvalent metal and the amount of the monovalent metal.
[0184] The complex elastic modulus of the toner at 65°C is preferably 1.0×10 7 Pa to 5.0×10 7 Pa, the complex elastic modulus at 85°C is preferably 1.0×10 5 Pa or less. When the complex elastic modulus at 65°C is 1.0×10 7 Pa to 5.0×10 7 Pa, it is preferred to form a crosslink between the polar part and at least one of the polyvalent metal and the monovalent metal, and can exhibit excellent effects of suppressing development streaks and charge retention. In addition, when the complex elastic modulus at 85°C is 1.0×10 5 Pa or less, the crosslinking between the polar portion and at least one of the polyvalent metal and the monovalent metal exhibits suitable strength to relax when exceeding the melting point, and excellent low-temperature fixing property can be exhibited.
[0185] The complex elastic modulus of the toner at 65°C is preferably 2.0×10 7 Pa to 4.0×10 7 Pa. In addition, the complex elastic modulus of the toner at 85°C is preferably 9.5×10 4 Below Pa.
[0186] The domain diameter of at least one of the polyvalent metal and the monovalent metal is preferably 10 nm to 50 nm as determined by mapping image analysis of a toner particle cross section using an energy dispersive X-ray spectrometer (EDX) of a scanning electron microscope (SEM). The method for measuring the domain diameter of at least one of the polyvalent metal and the monovalent metal will be described below.
[0187] When the domain diameter is within the above range, a microphase separation state caused by the polarity difference between the monomer units is advantageously formed. As a result, the non-crosslinked part that contributes to low-temperature fixability and charge retention and the crosslinked part that contributes to the effect of suppressing development streaks can be present in the form of a domain matrix. Therefore, a toner having excellent low-temperature fixability, the effect of suppressing development streaks and charge retention can be obtained. The domain diameter can be adjusted by the type and amount of the second monomer unit.
[0188] The domain diameter is more preferably from 30 nm to 50 nm.
[0189] This microphase separation state can be observed by marking at least one of the polyvalent metal and the monovalent metal oriented to the polar portion and observing it with SEM.
[0190] The polymer may include a third monomer unit derived from a third polymerizable monomer, which is not included in the scope of formula (1) or (2) (i.e., a polymerizable monomer different from the first polymerizable monomer and the second polymerizable monomer), in an amount that does not impair the above-mentioned molar ratio of the first monomer unit derived from the first polymerizable monomer and the second monomer unit derived from the second polymerizable monomer.
[0191] Among the monomers exemplified as the second polymerizable monomer, those which do not satisfy formula (1) or formula (2) can be used as the third polymerizable monomer.
[0192] In addition, the following monomers can be used. For example, styrene and its derivatives such as styrene, o-methylstyrene, etc., and (meth)acrylates such as methyl (meth)acrylate, n-butyl (meth)acrylate, tert-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, etc. In addition, when formula (1) or formula (2) is satisfied, such monomers can be used as the second polymerizable monomer.
[0193] In order to improve the storability of the toner, the third polymerizable monomer is preferably at least one selected from the group consisting of styrene, methyl methacrylate, and methyl acrylate.
[0194] The acid value of the polymer A is preferably 30.0 mg KOH / g or less, more preferably 20.0 mg KOH / g or less.
[0195] When the acid value is within the above range, the hygroscopicity under high temperature and high humidity environment is low, and thus excellent charge retention can be exhibited. The lower limit of the acid value is not particularly limited, but is preferably 0 mg KOH / g or more.
[0196] The polymer A preferably has a weight average molecular weight (Mw) of tetrahydrofuran (THF) insoluble matter measured by gel permeation chromatography (GPC) of 10,000 to 200,000, more preferably 20,000 to 150,000. When the Mw is within the above range, elasticity near room temperature can be easily maintained.
[0197] The polymer A preferably has a melting point of 50° C. to 80° C., more preferably 53° C. to 70° C. When the melting point of the polymer A is within the above range, excellent low-temperature fixing property is exhibited.
[0198] The melting point of the polymer A can be adjusted by the type and amount of the first polymerizable monomer and the type and amount of the second polymerizable monomer to be used, and the like.
[0199] The polymer A is preferably a vinyl polymer. Examples of the vinyl polymer include polymers of monomers including an ethylenically unsaturated bond. An ethylenically unsaturated bond refers to a carbon-carbon double bond capable of free radical polymerization, and examples thereof include vinyl, propylene, acryloyl, methacryloyl, and the like.
[0200] <Resin Different from Polymer A>
[0201] If necessary, the binder resin may also include a resin other than the polymer A. The resin other than the polymer A to be used for the binder resin can be exemplified by the following resins.
[0202] Homopolymers of styrene and its substitution products such as polystyrene, poly(p-chlorostyrene), polyvinyltoluene, etc.; styrene copolymers such as styrene-p-chlorostyrene copolymer, styrene-vinyltoluene copolymer, styrene-vinylnaphthalene copolymer, styrene-acrylate copolymer, styrene-methacrylate copolymer, styrene-α-chloromethyl methacrylate copolymer, styrene-acrylonitrile copolymer, styrene-vinyl methyl ether copolymer, styrene-vinyl ethyl ether copolymer, styrene-vinyl methyl ketone copolymer, styrene-acrylonitrile-indene copolymer; polyvinyl chloride, phenolic resin, phenolic resin modified by natural resin, maleic resin modified by natural resin, acrylic resin, methacrylic resin, polyvinyl acetate, silicone resin, polyester resin, polyurethane resin, polyamide resin, furan resin, epoxy resin, xylene resin, polyvinyl butyral, terpene resin, coumarone-indene resin, petroleum resin, etc.
[0203] Among these, styrene copolymers and polyester resins are preferred. Furthermore, it is preferred that the resin other than the polymer A is amorphous.
[0204] In addition, when the amount of polymer A in the binder resin is 50.0% by mass or more, excellent low-temperature fixability can be exhibited. More preferably, the amount is 80.0% by mass to 100.0% by mass, and more preferably, the binder resin is polymer A.
[0205] <Release Agent>
[0206] The toner particles may include wax as a release agent. Examples of such waxes are given below.
[0207] Hydrocarbon waxes such as low molecular weight polyethylene, low molecular weight polypropylene, alkylene copolymers, microcrystalline wax, paraffin wax, Fischer-Tropsch wax, etc.; oxides of hydrocarbon waxes such as oxidized polyethylene wax or their block copolymers; waxes based on fatty acid esters such as carnauba wax; and partially or fully deoxygenated fatty acid esters such as deoxygenated carnauba wax. Saturated straight-chain fatty acids such as palmitic acid, stearic acid and montanic acid; unsaturated fatty acids such as brashidic acid; acid), eleostearic acid and valinaric acid; saturated alcohols such as stearyl alcohol, aralkyl alcohol, behenyl alcohol, carnauba alcohol, wax alcohol and myricol; polyols such as sorbitol; esters of fatty acids such as palmitic acid, stearic acid, behenic acid and montanic acid with alcohols such as stearyl alcohol, aralkyl alcohol, behenyl alcohol, carnauba alcohol, wax alcohol and myricol; fatty acid amides such as linoleic acid amide, oleic acid amide and lauric acid amide; saturated fatty acid bisamides such as methylene bisstearic acid amide, ethylene biscapric acid amide, ethylene bislauric acid amide and hexamethylene bisstearic acid amide; unsaturated fatty acid acyl esters such as 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 61, 62, 63, 64, 65, 66, 67, 68, 70, 71, 72, 73, 74, 75 Amines such as ethylenebisoleamide, hexamethylenebisoleamide, N,N'-dioleyl adipamide and N,N'-dioleyl sebacic acid amide; aromatic bisamides such as m-xylene bisstearamide and N,N'-distearylisophthalic acid amide; aliphatic metal salts such as calcium stearate, calcium laurate, zinc stearate and magnesium stearate (commonly known as metal soaps); waxes obtained by grafting vinyl monomers such as styrene and acrylic acid onto aliphatic hydrocarbon waxes; partial esterification products of fatty acids and polyols such as glycerol monoester behenate; and methyl ester compounds having a hydroxyl group obtained by hydrogenating vegetable fats and oils.
[0208] Among these waxes, hydrocarbon waxes such as paraffin wax and Fischer-Tropsch wax and fatty acid ester waxes such as carnauba wax are preferred from the viewpoint of improving low-temperature fixability and fixation separation property. Hydrocarbon waxes are more preferred because hot offset resistance is further improved.
[0209] The amount of the wax is preferably 3 parts by mass to 8 parts by mass relative to 100 parts by mass of the binder resin.
[0210] In an endothermic curve at a temperature increase measured using a differential scanning calorimeter (DSC) apparatus, the peak temperature of the maximum endothermic peak of the wax is preferably 45 to 140° C. When the peak temperature of the maximum endothermic peak of the wax is within the above range, storability and hot offset resistance of the toner can be achieved.
[0211] <Colorant>
[0212] If necessary, the toner may include a colorant. Examples of the colorant are given below.
[0213] Examples of black colorants include carbon black and colorants toned in black by using yellow colorants, magenta colorants and cyan colorants. Pigments can be used alone, and dyes and pigments can be used in combination as colorants. From the viewpoint of image quality of full-color images, dyes and pigments are preferably used in combination.
[0214] Examples of pigments for magenta toners are given below. CI Pigment Red 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 21, 22, 23, 30, 31, 32, 37, 38, 39, 40, 41, 48:2, 48:3, 48:4, 49, 50, 51, 52, 53, 54, 55, 57:1, 58, 6 0,63,64,68,81:1,83,87,88,89,90,112,114,122,123,146,147,150,163,184,202,206,207,209,238,269,282; CI Pigment Violet 19; and CI Vat Red 1,2,10,13,15,23,29,35.
[0215] Examples of dyes for magenta toners are given below: CI Solvent Red 1, 3, 8, 23, 24, 25, 27, 30, 49, 81, 82, 83, 84, 100, 109, 121; CI Disperse Red 9; CI Solvent Violet 8, 13, 14, 21, 27; oil-soluble dyes such as CI Disperse Violet 1; CI Basic Red 1, 2, 9, 12, 13, 14, 15, 17, 18, 22, 23, 24, 27, 29, 32, 34, 35, 36, 37, 38, 39, 40; and basic dyes such as CI Basic Violet 1, 3, 7, 10, 14, 15, 21, 25, 26, 27, 28.
[0216] Examples of pigments for cyan toners are given below: CI Pigment Blue 2, 3, 15:2, 15:3, 15:4, 16, 17; CI Vat Blue 6; CI Acid Blue 45 and copper phthalocyanine pigments in which 1 to 5 phthalimidomethyl groups are substituted in the phthalocyanine skeleton.
[0217] CI Solvent Blue 70 is an example of a dye for cyan toner.
[0218] Examples of pigments for yellow toners are given below: CI Pigment Yellow 1, 2, 3, 4, 5, 6, 7, 10, 11, 12, 13, 14, 15, 16, 17, 23, 62, 65, 73, 74, 83, 93, 94, 95, 97, 109, 110, 111, 120, 127, 128, 129, 147, 151, 154, 155, 168, 174, 175, 176, 180, 181, 185; and CI Vat Yellow 1, 3, 20.
[0219] CI Solvent Yellow 162 is an example of a dye for yellow toner.
[0220] These colorants may be used alone or in a mixture, or in the form of a solid solution. The colorant is selected from the viewpoints of hue angle, saturation, brightness, light resistance, OHP transparency, and dispersibility in the toner.
[0221] The amount of the colorant is preferably 0.1 parts by mass to 30.0 parts by mass relative to the total amount of the resin components.
[0222] <Charge Control Agent>
[0223] The toner particles may optionally include a charge control agent. By blending the charge control agent, it is possible to stabilize the charge characteristics and control the optimum triboelectric charge amount according to the developing system.
[0224] As the charge control agent, known ones can be used, but in particular, a metal compound of an aromatic carboxylic acid which is colorless, can accelerate the charging speed of the toner and can stably maintain a constant charge amount is preferable.
[0225] Examples of negative charge control agents include salicylic acid metal compounds, naphthoic acid metal compounds, dicarboxylic acid metal compounds, polymer compounds having sulfonic acid or carboxylic acid on the side chain, polymer compounds having sulfonates or sulfonates on the side chain, polymer compounds having carboxylates or carboxylates on the side chain, boron compounds, urea compounds, organosilicon compounds, and calixarene.
[0226] The charge control agent may be added to the toner particles internally or externally. The amount of the charge control agent is preferably 0.2 parts by mass to 10.0 parts by mass, more preferably 0.5 parts by mass to 10.0 parts by mass, relative to 100 parts by mass of the binder resin.
[0227] <Inorganic fine particles>
[0228] If necessary, the toner may include inorganic fine particles.
[0229] The inorganic fine particles may be added internally to the toner particles, or may be mixed with the toner as an external additive. Examples of the inorganic fine particles include fine particles such as silica fine particles, titanium oxide fine particles, aluminum oxide fine particles, or fine particles of their composite oxides. Among the inorganic fine particles, silica fine particles and titanium oxide fine particles are preferred from the viewpoint of fluidity improvement and charging uniformity.
[0230] The inorganic fine particles are preferably hydrophobized with a hydrophobizing agent such as a silane compound, silicone oil, or a mixture thereof.
[0231] From the viewpoint of improving fluidity, the inorganic fine particles as the external additive preferably have a particle size of 50 μm. 2 / g to 400m 2 From the viewpoint of improving durable stability, the inorganic fine particles as external additives preferably have a specific surface area of 10 m 2 / g to 50m 2 In order to simultaneously ensure improved fluidity and durable stability, inorganic fine particles having a specific surface area within these ranges may be used in combination.
[0232] The amount of the external additive is preferably 0.1 parts by mass to 10.0 parts by mass relative to 100 parts by mass of the toner particles.A known mixer such as a Henschel mixer can be used to mix the toner particles with the external additive.
[0233] <Developer>
[0234] The toner can be used as a one-component developer, but is preferably used as a two-component developer by mixing with a magnetic carrier in order to further improve dot reproducibility and provide a stable image over a long period of time.
[0235] Examples of magnetic carriers include well-known materials such as iron oxide; metal particles such as iron, lithium, calcium, magnesium, nickel, copper, zinc, cobalt, manganese, chromium and rare earth metals, their alloy particles and their oxide particles; magnetic bodies such as ferrite; magnetic body dispersion resin carriers (so-called resin carriers) comprising a magnetic body and a binder resin for maintaining the magnetic body in a dispersed state.
[0236] When the toner is used as a two-component developer by mixing with a magnetic carrier, the mixing ratio of the magnetic carrier at this time is preferably 2% by mass to 15% by mass, more preferably 4% by mass to 13% by mass, as a toner concentration in the two-component developer.
[0237] <Toner Production Method>
[0238] The production method of the toner of the present invention is not particularly limited, and known methods such as a pulverization method, a suspension polymerization method, a dissolution suspension method, an emulsion aggregation method, and a dispersion polymerization method can be used.
[0239] Here, the toner of the present invention is preferably produced by the following method. Therefore, the toner of the present invention is preferably produced by an emulsion aggregation method.
[0240] The production method of toner includes:
[0241] a step of preparing a resin fine particle dispersion liquid including a binder resin;
[0242] a step of adding a flocculant to the resin fine particle dispersion to form aggregated particles; and
[0243] a step of heating and fusing the aggregated particles to obtain a dispersion liquid including toner particles, wherein
[0244] The binder resin includes a polymer A,
[0245] Polymer A is a polymer of the composition comprising:
[0246] a first polymerizable monomer, and
[0247] a second polymerizable monomer different from the first polymerizable monomer;
[0248] The first polymerizable monomer is at least one selected from the group consisting of (meth)acrylates having an alkyl group having 18 to 36 carbon atoms;
[0249] The content of the first polymerizable monomer in the composition is 5.0 mol % to 60.0 mol % based on the total moles of all polymerizable monomers in the composition;
[0250] The content of the second polymerizable monomer in the composition is 20.0 mol % to 95.0 mol % based on the total moles of all polymerizable monomers in the composition;
[0251] The SP value of the first polymerizable monomer is determined by SP 12 (J / cm 3 ) 0.5 The SP value of the second polymerizable monomer is represented by SP 22 (J / cm 3 ) 0.5 In the case of , the above equations (4) and (5) are satisfied;
[0252] Flocculants include polyvalent metals;
[0253] The multivalent metal is at least one selected from the group consisting of Mg, Ca, Al and Zn; and
[0254] The content of the polyvalent metal in the toner particles is 25 ppm to 500 ppm by mass.
[0255] In the case of the above-mentioned production method, two or more types of monomer units with greatly different polarities form a microphase separation state in the toner particles. The polyvalent metal is oriented to the polar part, and a crosslink between the polyvalent metal and the polar part is formed. As a result, a non-crosslinked part that contributes to low-temperature fixability and charge retention and a crosslinked part that contributes to suppressing development stripes can be formed in a network throughout the toner particles, and a domain matrix structure in which a domain phase composed of the crosslinked part is dispersed in a matrix phase composed of the non-crosslinked part is formed. Therefore, a toner having excellent low-temperature fixability, an effect of suppressing development stripes under high temperature and high humidity environments, and charge retention can be obtained.
[0256] <Emulsion Aggregation Method>
[0257] In the emulsion aggregation method, an aqueous dispersion of fine particles sufficiently smaller than a desired particle size and composed of constituent materials of toner particles is prepared in advance, the fine particles are aggregated to the particle size of toner particles in an aqueous medium, and the resin is melted by heating or the like to prepare toner particles.
[0258] That is, in the emulsion aggregation method, the toner particles are prepared by a dispersion step of preparing a fine particle dispersion composed of the constituent materials of the colorant particles, an aggregation step of aggregating the fine particles composed of the constituent materials of the colorant particles and controlling the particle size until the particle size of the colorant particles is obtained, a melting step of melting the resin contained in the obtained aggregated particles, a subsequent cooling step, a metal removal step of filtering out the obtained colorant and removing excess polyvalent metal ions, a filtration and washing step of washing with ion exchange water or the like, and a step of removing moisture from the washed colorant particles and drying them.
[0259] In the emulsion aggregation method, the step of contacting the toner particles with an organic solvent and the separation step correspond to the step of treating the wet cake of the toner particles obtained in the filtering and washing steps with an organic solvent, or the step of treating the toner particles finally obtained by the drying step with an organic solvent.
[0260] <Step of Preparing Resin Fine Particle Dispersion Liquid (Dispersion Step)>
[0261] The resin fine particle dispersion can be prepared by known methods, but is not limited to these methods. Examples of the known methods include an emulsion polymerization method, a self-emulsification method, a phase inversion emulsification method in which a resin is emulsified by adding an aqueous medium to a resin solution obtained by dissolving a resin in an organic solvent, and a forced emulsification method in which the resin is forcibly emulsified by high-temperature treatment in an aqueous medium without using an organic solvent.
[0262] Specifically, the binder resin is dissolved in an organic solvent that can dissolve the resin, and a surfactant or an alkaline compound is added. At this time, in the case where the binder resin is a crystalline resin with a melting point, the resin can be dissolved by melting to a temperature higher than the melting point. Subsequently, an aqueous medium is slowly added to precipitate the fine resin particles while stirring with a homogenizer or the like. Then, the solvent is removed by heating or decompression to prepare a fine resin particle dispersion aqueous solution. Any organic solvent that can dissolve the resin can be used as an organic solvent for dissolving the resin, but from the viewpoint of suppressing the generation of coarse powder, an organic solvent such as toluene that preferably forms a homogeneous phase with water.
[0263] The surfactant used in emulsification is not particularly limited, and examples thereof include ionic surfactants such as sulfates, sulfonates, carboxylates, phosphates, soaps, etc.; cationic surfactants such as amine salts, quaternary ammonium salts, etc.; and nonionic surfactants such as polyethylene glycol, alkylphenol ethylene oxide adducts, polyols, etc. The surfactant may be used alone or in combination of two or more thereof.
[0264] Examples of the basic compound used in the dispersing step include inorganic bases such as sodium hydroxide, potassium hydroxide, etc., and organic bases such as ammonia, triethylamine, trimethylamine, dimethylaminoethanol, diethylaminoethanol, etc. The basic compound may be used alone or in combination of two or more thereof.
[0265] The 50% particle size (D50) based on volume distribution of the fine particles of the binder resin in the resin fine particle dispersion aqueous solution is preferably 0.05 μm to 1.0 μm, more preferably 0.05 μm to 0.4 μm. By adjusting the 50% particle size (D50) based on volume distribution to the above range, it is easy to obtain toner particles having a volume average particle size of 3 μm to 10 μm suitable for toner particles.
[0266] A dynamic light scattering type particle size distribution analyzer NANOTRAC UPA-EX150 (manufactured by Nikkiso Co., Ltd.) was used to measure the 50% particle diameter (D50) based on volume distribution.
[0267] <Colorant Fine Particle Dispersion Liquid>
[0268] The colorant fine particle dispersion liquid used as necessary can be prepared by known methods listed below, but is not limited to these methods.
[0269] The colorant fine particle dispersion can be prepared by mixing the colorant, the aqueous medium and the dispersant using a mixer such as a known stirrer, an emulsifier and a disperser. The dispersant used here may be a known dispersant such as a surfactant and a polymer dispersant.
[0270] Although any surfactant and polymer dispersant may be removed in the washing step described below, a surfactant is preferred from the viewpoint of washing efficiency.
[0271] Examples of the surfactant include ionic surfactants such as sulfates, sulfonates, carboxylates, phosphates, soaps, etc.; cationic surfactants such as amine salts, quaternary ammonium salts, etc.; and nonionic surfactants such as polyethylene glycol, alkylphenol ethylene oxide adducts, polyols, etc.
[0272] Among these, nonionic surfactants and ionic surfactants are preferred. In addition, nonionic surfactants and anionic surfactants can be used together. Surfactants can be used alone or in two or more combinations thereof. The concentration of the surfactant in the aqueous medium is preferably 0.5% by mass to 5% by mass.
[0273] The amount of the colorant fine particles in the colorant fine particle dispersion liquid is not particularly limited, but it is preferably 1% by mass to 30% by mass relative to the total mass of the colorant fine particle dispersion liquid.
[0274] In addition, from the viewpoint of the dispersibility of the colorant in the final toner, the dispersed particle size of the colorant fine particles in the colorant fine particle dispersion aqueous solution is preferably such that the 50% particle size (D50) based on the volume distribution is 0.5 μm or less. In addition, for the same reason, the 90% particle size (D90) based on the volume distribution is preferably 2 μm or less. The dispersed particle size of the colorant particles dispersed in the aqueous medium is measured by a dynamic light scattering type particle size distribution analyzer (NANOTRAC UPA-EX150: manufactured by Nikkiso Co., Ltd.).
[0275] Known mixers such as stirrers, emulsifiers and dispersers for dispersing the colorant in the aqueous medium include ultrasonic homogenizers, jet mills, pressure homogenizers, colloid mills, ball mills, sand mills and paint shakers. These can be used alone or in combination.
[0276] <Release Agent (Aliphatic Hydrocarbon Compound) Fine Particle Dispersion>
[0277] The release agent fine particle dispersion may be used as required. The release agent fine particle dispersion may be prepared by the following known methods, but is not limited to these methods.
[0278] The releasing agent fine particle dispersion can be prepared by adding the releasing agent to an aqueous medium including a surfactant, heating to a temperature equal to or higher than the melting point of the releasing agent, dispersing into a particle shape using a homogenizer having a strong shearing ability (e.g., "CLEARMIX W MOTION" manufactured by M Technique Co., Ltd.) or a pressure discharge type disperser (e.g., "GAULIN HOMOGENIZER" manufactured by Gaulin Co., Ltd.), and then cooling to below the melting point.
[0279] The dispersion particle size of the release agent fine particle dispersion in the release agent aqueous dispersion is preferably such that the 50% particle size (D50) based on volume distribution is 0.03 to 1.0 μm, more preferably 0.1 to 0.5 μm. In addition, preferably no coarse particles of 1 μm or more are present.
[0280] When the dispersed particle size of the release agent fine particle dispersion is within the above range, the release agent can be finely dispersed to be present in the toner, the bleeding effect during fixing can be maximized, and good separability can be obtained. The dispersed particle size of the release agent fine particle dispersion obtained by dispersing in an aqueous medium can be measured by using a dynamic light scattering type particle size distribution analyzer (NANOTRAC UPA-EX 150: manufactured by Nikkiso Co., Ltd.).
[0281] <Mixing Step>
[0282] In the mixing step, if necessary, a mixed liquid is prepared by mixing the resin fine particle dispersion with at least one of a releasing agent fine particle dispersion and a colorant fine particle dispersion. The mixing can be performed using a known mixing device such as a homogenizer and a mixer.
[0283] <Step of Forming Aggregated Particles (Aggregation Step)>
[0284] In the aggregation step, the fine particles contained in the mixed liquid prepared in the mixing step are aggregated to form aggregates having a target particle size. At this time, a flocculant is added and mixed, and if necessary, at least one of heating and mechanical power is appropriately added to form aggregates in which fine resin particles and at least one of release agent fine particles and colorant fine particles (if necessary) are aggregated.
[0285] The flocculant is a flocculant including metal ions of a multivalent metal, the multivalent metal being at least one selected from the group consisting of Mg, Ca, Al, and Zn.
[0286] The flocculant including the metal ion of the polyvalent metal has a high aggregation ability, and this purpose can be achieved by adding a small amount of metal ions. These flocculants can ionically neutralize the ionic surfactants contained in the resin fine particle dispersion, the release agent fine particle dispersion and the colorant fine particle dispersion. As a result, the binder resin fine particles, the release agent fine particles and the colorant fine particles are aggregated by salting out and ionic crosslinking effects. In addition, the flocculant including the metal ion of the polyvalent metal can form crosslinks with the polymer. As a result, the crosslinking points of the polar parts of the polyvalent metal and the toner particles can be formed in a network in the entire toner particles, and a domain matrix structure is formed at the same time. Therefore, excellent charge retention can be shown without damaging low-temperature fixability, and development stripes can be suppressed.
[0287] The flocculant comprising the metal ion of a polyvalent metal can exemplify the metal salt of a polyvalent metal and the polymer of the metal salt. Specific examples include divalent inorganic metal salts such as calcium chloride, calcium nitrate, magnesium chloride, magnesium sulfate and zinc chloride. Other examples include trivalent metal salts such as iron (III) chloride, iron (III) sulfate, aluminum sulfate and aluminum chloride. In addition, inorganic metal salt polymers such as polyaluminum chloride, polyaluminum hydroxide and calcium polysulfide can be mentioned, but these examples are not restrictive. These can be used alone or in combination of two or more thereof.
[0288] The flocculant may be added in the form of a dry powder or an aqueous solution obtained by dissolving in an aqueous medium, but in order to cause uniform aggregation, the flocculant is preferably added in the form of an aqueous solution.
[0289] In addition, it is preferred to add and mix the flocculant at a temperature equal to or lower than the glass transition temperature or melting point of the resin contained in the mixed liquid. By mixing under such temperature conditions, aggregation is relatively uniform. The mixing of the flocculant into the mixed liquid can be carried out using known mixing equipment such as a homogenizer and a mixer. The aggregation step is a step of forming aggregates of the toner particle size in an aqueous medium. The volume average particle size of the aggregates prepared in the aggregation step is preferably 3μm to 10μm. The volume average particle size can be measured by the Coulter method using a particle size distribution analyzer (Coulter Multisizer III: manufactured by Beckman Coulter, Inc.).
[0290] <Step of Obtaining a Dispersion Liquid Including Toner Particles (Melting Step)>
[0291] In the melting step, an aggregation stopper is added to the dispersion liquid including the aggregates obtained in the aggregation step under stirring similar to that in the aggregation step. The aggregation stopper can be exemplified by a chelating agent that stabilizes aggregated particles by dissociating the ion crosslinking part between the acidic polar group of the surfactant and the metal ion as a flocculant and forming a coordinate bond with the metal ion. By adding the aggregation stopper, the crosslinking points between the polar part of the toner particles and the multivalent metal can be controlled to an optimal amount, so that an excellent effect of suppressing development streaks and excellent charge retention can be exhibited without impairing low-temperature fixability.
[0292] After the dispersion state of the aggregated particles in the dispersion liquid is stabilized by the action of the aggregation stopper, the aggregated particles are melted by heating to a temperature equal to or higher than the glass transition temperature or melting point of the binder resin.
[0293] The chelating agent is not particularly limited as long as it is a known water-soluble chelating agent. Specific examples include hydroxycarboxylic acids such as tartaric acid, citric acid and gluconic acid, and their sodium salts; iminodiacid (IDA), nitrilotriacetic acid (NTA) and ethylenediaminetetraacetic acid (EDTA), and sodium salts of these acids.
[0294] The chelating agent coordinates with the metal ions of the flocculant present in the dispersion of aggregated particles, so that the environment in the dispersion can be changed from an electrostatically unstable state where aggregation is likely to occur to an electrostatically stable state where further aggregation is unlikely to occur. As a result, further aggregation of aggregated particles in the dispersion can be suppressed and the aggregated particles can be stabilized.
[0295] The chelating agent is preferably an organic metal salt of a carboxylic acid having a valence of 3 or more, since even a small amount of such a chelating agent is effective and toner particles having a sharp particle size distribution can be obtained.
[0296] Furthermore, from the viewpoint of achieving both stabilization of the aggregation state and washing efficiency, the amount of the chelating agent added is preferably 1 to 30 parts by mass, more preferably 2.5 to 15 parts by mass, relative to 100 parts by mass of the binder resin. The 50% particle size (D50) based on volume of the toner particles is preferably 3 to 10 μm.
[0297] <Cooling Step>
[0298] If necessary, in the cooling step, the temperature of the dispersion liquid including the toner particles obtained in the melting step may also be lowered to a temperature lower than at least one of the crystallization temperature and the glass transition temperature of the binder resin. By cooling to a temperature lower than at least one of the crystallization temperature and the glass transition temperature, the generation of coarse particles can be prevented. The specific cooling rate may be 0.1° C. / min to 50° C. / min.
[0299] <Metal Removal Step>
[0300] Furthermore, it is preferred that the toner production method includes a metal removal step of removing the metal by adding a chelate compound having a chelate ability with respect to metal ions to a dispersion liquid including toner particles. By the metal removal step, the concentration distribution of the polyvalent metal in the cross section of the toner particles can be controlled. Specifically, since the polyvalent metal concentration in the surface layer of the toner particles can be made lower than the polyvalent metal concentration in the interior of the toner particles, an excellent effect of suppressing development streaks and charge retention are exhibited without impairing low-temperature fixability.
[0301] The chelate compound is not particularly limited as long as it is a known water-soluble chelate, and the above-mentioned chelates can be used. Since the metal removal performance of the water-soluble chelate is very sensitive to temperature, the metal removal step is preferably performed at 40 to 60°C, more preferably at about 50°C.
[0302] <Washing Steps>
[0303] If necessary, impurities in the toner particles can be removed by repeatedly washing and filtering the toner particles obtained in the cooling step in the washing step. Specifically, it is preferred to wash the toner particles with an aqueous solution including a chelating agent such as ethylenediaminetetraacetic acid (EDTA) and its Na salt, and further wash with pure water. By repeatedly washing and filtering with pure water for multiple times, metal salts and surfactants in the toner particles can be removed. From the viewpoint of production efficiency, the number of filtrations is preferably 3 to 20, more preferably 3 to 10.
[0304] <Drying Step>
[0305] In the drying step, the toner particles obtained in the above steps are dried, if necessary.
[0306] <External addition steps>
[0307] In the external adding step, if necessary, inorganic fine particles are externally added to the toner particles obtained in the drying step. Specifically, inorganic fine particles such as silica or resin fine particles of a vinyl resin, polyester resin or silicone resin are preferably added while applying a shear force in a dry state.
[0308] Methods of measuring various physical properties of toner particles and raw materials will be described below.
[0309] <Method for measuring the amount of metal in toner particles>
[0310] The amount of metal in the toner particles is measured using a multi-element simultaneous type ICP emission spectrophotometer Vista-PRO (manufactured by Hitachi High-TechScience Co., Ltd.).
[0311] Sample: 50mg
[0312] Solvent: 6 mL of nitric acid
[0313] The above materials were weighed and subjected to decomposition treatment using a microwave sample pretreatment device ETHOS UP (manufactured by Milestone General Co., Ltd.).
[0314] Temperature: Increase from 20°C to 230°C and maintain at 230°C for 30 min.
[0315] The decomposed solution is passed through filter paper (5C), transferred to a 50 mL volumetric flask, and made up to 50 mL with ultrapure water. The amount of multivalent metal elements (e.g., Mg, Ca, Al, and Zn) and monovalent metal elements (Na, Li, and K) in the toner particles can be quantified by measuring the aqueous solution in the volumetric flask using a multi-element simultaneous ICP emission spectrophotometer Vista-PRO under the following conditions. In order to quantify the amount, a calibration curve is prepared using a standard sample of the element to be quantified, and calculation is performed based on the calibration curve.
[0316] Conditions: RF power 1.20kW,
[0317] Ar gas: plasma flow 15.0L / min,
[0318] Auxiliary flow: 1.50L / min,
[0319] MFC: 1.50L / min,
[0320] Nevizer flow: 0.90L / min,
[0321] Pumping speed: 15rpm,
[0322] Measurement repetition: 3 times,
[0323] Measuring time: 1.0s
[0324] (Measurement of the case where a toner to which inorganic fine particles including at least one metal selected from the group consisting of Mg, Ca, Al and Zn are externally added)
[0325] When measuring the amount of metal in toner particles of a toner to which inorganic fine particles including at least one metal selected from the group consisting of Mg, Ca, Al and Zn are externally added, the measurement is performed after the inorganic fine particles are separated from the toner to prevent calculation of the amount of metal derived from the inorganic fine particles other than the metal forming a crosslink with the polar portion.
[0326] (Method of Separating Material from Toner)
[0327] By utilizing the difference in solubility of various materials contained in the toner in the solvent, the materials can be separated from the toner.
[0328] First separation: The toner is dissolved in methyl ethyl ketone (MEK) at 23° C., and soluble matter (amorphous resin other than polymer A) and insoluble matter (polymer A, releasing agent, colorant, inorganic fine particles, etc.) are separated.
[0329] Second separation: The insoluble matter (polymer A, release agent, colorant, inorganic fine particles, etc.) obtained in the first separation is dissolved in MEK at 100°C, and the soluble matter (polymer A, release agent) and the insoluble matter (colorant, inorganic fine particles, etc.) are separated.
[0330] Third separation: The soluble matter (polymer A, releasing agent) obtained in the second separation was dissolved in chloroform at 23°C, and the soluble matter (polymer A) and the insoluble matter (releasing agent) were separated.
[0331] <Method of Measuring Metal Domain Diameter in Cross Section of Toner Particle and Method of Measuring Concentration Distribution of Polyvalent Metal in Cross Section of Toner Particle>
[0332] The metal domain diameter in the cross section of the toner particle and the concentration distribution of the polyvalent metal in the cross section of the toner particle were measured by metal mapping measurement using a scanning electron microscope S-4800 (manufactured by Hitachi High-Tech Science Co., Ltd.) and an energy dispersive X-ray analyzer EDAX 204B. The cross section of the toner particle to be observed was selected in the following manner. First, the cross-sectional area of the toner particle was determined from the cross-sectional image of the toner particle, and the diameter of a circle having an area equal to the cross-sectional area (equivalent circle diameter) was determined. Only the cross-sectional image of the toner particle whose absolute value of the difference between the equivalent circle diameter of the toner and the weight-average particle diameter (D4) was within 1.0 μm was observed.
[0333] Accelerating voltage: 20 kV
[0334] Magnification: 10,000x
[0335] The distance between the two points farthest from each other in the portion where the plotted points are continuous is measured and taken as the domain diameter. In addition, the concentration distribution of the polyvalent metal can be determined by calculating the metal concentration of the resin component in the region from the toner particle surface to a depth of 0.4 μm and the metal concentration of the resin component in the region deeper than 0.4 μm from the toner particle surface in the depth direction of the toner particle from the toner particle surface to the toner particle center. The metal concentrations in the region from the toner particle surface to a depth of 0.4 μm and the region deeper than 0.4 μm from the toner particle surface are calculated from 100 toner particles, and the average value of the 100 toner particles is taken as each metal concentration.
[0336] As a specific method, the captured image is binarized and calculated using the image processing software Image-Pro Plus5.1J (manufactured by Media Cybernetics, Inc.). First, a portion of the toner particle group is extracted, and the size of an extracted toner particle is calculated. Specifically, first, the toner particle group and the background portion are separated to extract the toner particle group to be analyzed. Then, "MEASUREMENT"-"COUNT / SIZE" in Image-Pro Plus5.1J is selected. In the "BRIGHTNESS RANGE SELECTION" of "COUNT / SIZE", the brightness range is set within the range of 50 to 255, the carbon ribbon portion with low brightness as background reflection is excluded, and the toner particle group is extracted. When extracting, 4 connections are selected in the "COUNT / SIZE" extraction option, the smoothness is set to 5, and "FILL IN HOLES" is selected. Through this operation, the toner particles located on all boundaries (periphery) of the image and the toner particles overlapping with other toner particles are excluded from the calculation. Next, "AREA AND FERET'S DIAMETER (AVERAGE)" is selected in the "COUNT / SIZE" measurement item, and the toner particles to be subjected to image analysis are extracted, with the area selection range being a minimum of 100 pixels and a maximum of 10,000 pixels. One toner particle is selected from the extracted toner particle group, and the size (number of pixels) js of the portion originating from the area from the toner particle surface to a depth of 0.4 μm is measured. The size (number of pixels) ji of the portion originating from an area deeper than 0.4 μm from the surface is measured in a similar manner.
[0337] Next, the size (number of pixels) ms and mi of the portion where the plotted points are continuous in each area is measured. ms and mi are the total area of the scattered plotted points. The metal concentration s in the area from the toner particle surface to a depth of 0.4 μm is obtained from the obtained js and ms by using the following equation: 1 .
[0338] s 1 =(ms / js)×100
[0339] In a similar manner, the metal concentration s in the region deeper than 0.4 μm from the toner particle surface is obtained. 2 .
[0340] s 2 =(mi / ji)×100
[0341] Subsequently, the same process is performed for each toner particle of the extracted toner particle group until the number of selected toner particles reaches 100. When the number of toner particles in one field of view is less than 100, the same operation is repeated for the toner particle projected image in another field of view.
[0342] <Method for measuring the content of monomer units derived from various polymerizable monomers in polymer A>
[0343] The content of monomer units derived from various polymerizable monomers in polymer A was measured under the following conditions: 1 H-NMR was performed.
[0344] Measuring apparatus: FT NMR apparatus JNM-EX400 (manufactured by Nippon Denshi Co., Ltd.)
[0345] Measuring frequency: 400MHz
[0346] Pulse state: 5.0μs
[0347] Frequency range: 10500Hz
[0348] Cumulative times: 64 times
[0349] Measurement temperature: 30℃
[0350] Sample: 50 mg of the sample was placed in a sample tube with an inner diameter of 5 mm and deuterated chloroform (CDCl 3 ) as a solvent and dissolved in a thermostat at 40°C to prepare the sample.
[0351] From the peaks attributed to the constituent components of the monomer units derived from the first polymerizable monomer, the obtained 1 In the H-NMR chart, a peak independent of peaks attributed to constituent components of monomer units derived from other sources is selected, and the integrated value S of the peak is calculated. 1 .
[0352] Likewise, from the peaks attributable to the constituent components of the monomer units derived from the second polymerizable monomer, a peak independent of peaks attributable to constituent components of the monomer units derived from other sources is selected, and the integrated value S of the peak is calculated. 2 .
[0353] Furthermore, when a third polymerizable monomer is used, a peak independent of peaks attributed to constituent components of monomer units derived from other sources is selected from the peaks attributed to constituent components of monomer units derived from the third polymerizable monomer, and the integrated value S of the peak is calculated. 3 .
[0354] Use the integral value S 1 , S 2 and S 3 , the content of the monomer unit derived from the first polymerizable monomer is determined as follows. Here, n1, n2, and n3 are the numbers of hydrogen atoms in the constituent components to which the target peak in each fragment is attributed.
[0355] Content of monomer units derived from the first polymerizable monomer (mol%) = {(S 1 / n 1 ) / ((S 1 / n 1 )+(S 2 / n 2 )+(S 3 / n 3 ))}×100.
[0356] Similarly, the contents of the monomer units derived from the second polymerizable monomer and the third polymerizable monomer are determined as follows.
[0357] Content of monomer units derived from the second polymerizable monomer (mol%) = {(S 2 / n 2 ) / ((S 1 / n 1 )+(S 2 / n 2 )+(S 3 / n 3 ))}×100.
[0358] Content of monomer units derived from the third polymerizable monomer (mol%) = {(S 3 / n 3 ) / ((S 1 / n 1 )+(S 2 / n 2 )+(S 3 / n 3 ))}×100.
[0359] When using a polymerizable monomer other than vinyl that does not include a hydrogen atom in the constituent components in Polymer A, by using 13 C-NMR, the measurement nucleus is set to 13 C, and the measurement is performed in a single-pulse mode, and 1 H-NMR is calculated in the same manner.
[0360] In addition, when preparing a toner by suspension polymerization, the peaks of the release agent and other resins may overlap and independent peaks may not be observable. As a result, it may not be possible to calculate the content of monomer units derived from various polymerizable monomers in Polymer A. In such a case, Polymer A' can be prepared by the same suspension polymerization without using a release agent or other resins, and analysis can be performed by treating Polymer A' as Polymer A.
[0361] <SP Value Calculation Method>
[0362] According to the calculation method proposed by Fedors, the SP value of the polymerizable monomer and the SP value of the unit derived from the polymerizable monomer are determined as follows.
[0363] For each polymerizable monomer or release agent, the evaporation energy (Dei) (cal / mol) and molar volume (Δvi) (cm 3 / mol) of the atoms or atomic groups in the molecular structure are determined from the table described in "Polym. Eng. Sci., 14(2), 147 - 154(1974)", and (4.184×ΣΔei / ΣΔvi) 0.5 is taken as the SP value (J / cm 3 ) 0.5 .
[0364] In addition, SP 11 and SP 21 are calculated by the same calculation method as described above for the atoms or atomic groups in the molecular structure in the state where the double bond of the polymerizable monomer is cleaved by polymerization.
[0365] <Measurement of the Peak Molecular Weight and Weight-Average Molecular Weight of Polymer A and Resins Different from Polymer A by GPC>
[0366] The molecular weight (Mw) of the THF-soluble substances of Polymer A and resins different from Polymer A is measured by gel permeation chromatography (GPC) in the following manner.
[0367] First, the toner is dissolved in tetrahydrofuran (THF) at room temperature for 24 hours. Then, the resulting solution is filtered through a solvent-resistant membrane filter "Maishori Disk" (manufactured by Tosoh Corporation) with a pore size of 0.2 μm to obtain a sample solution. The sample solution is adjusted so that the concentration of the component dissolved in THF is about 0.8% by mass. By using this sample solution, measurement is performed under the following conditions.
[0368] Apparatus: HLC8120 GPC (detector: RI) (manufactured by Tosoh Corporation)
[0369] Column: 7 columns Shodex KF-801, 802, 803, 804, 805, 806, 807 (manufactured by Showa Denko KK)
[0370] Eluent: Tetrahydrofuran (THF)
[0371] Flow rate: 1.0mL / min
[0372] Oven temperature: 40.0℃
[0373] Sample injection volume: 0.10mL
[0374] The molecular weight of the sample is calculated using a molecular weight calibration curve prepared using a standard polystyrene resin (e.g., trade name "TSK standard polystyrene F-850, F-450, F-288, F-128, F-80, F-40, F-20, F-10, F-4, F-2, F-1, A-5000, A-2500, A-1000, A-500, manufactured by Tosoh Corporation).
[0375] <Method for measuring softening point of amorphous resin different from polymer A>
[0376] The softening point of an amorphous resin other than polymer A is measured by using a constant load extrusion capillary rheometer "Flow Characteristic Evaluation Device FLOW TESTER CFT-500D" (manufactured by Shimadzu Corporation) according to the manual provided with the device. Using this device, a measurement sample filled in a cylinder is heated and melted, and a constant load is applied from the top of the measurement sample by a piston, and the melted measurement sample is extruded from the die head at the bottom of the cylinder, and a flow curve representing the relationship between the piston descent amount and the temperature at this time can be obtained.
[0377] In the present invention, the "melting temperature in the 1 / 2 method" described in the manual provided with "Flow Characteristic Evaluation Device FLOW TESTER CFT-500D" is taken as the softening point.
[0378] The melting temperature in the 1 / 2 method is calculated as follows.
[0379] First, determine half (1 / 2) the difference between the piston drop at the end of outflow (end point of outflow, Smax) and the piston drop at the start of outflow (minimum point, Smin) (this is represented by X, X = (Smax-Smin / 2). When the piston drop is the sum of X and Smin, the temperature at the flow curve is the melting temperature in the 1 / 2 method.
[0380] By using a tablet press (eg, NT-100H, manufactured by NPa SYSTEM CO., LTD.), about 1.0 g of the resin is compression-molded at about 10 MPa for about 60 seconds at 25° C. to obtain a cylindrical sample having a diameter of about 8 mm for measurement.
[0381] Perform specific operations during measurement according to the manual provided with the device.
[0382] The measurement conditions of CFT-500D are as follows.
[0383] Test method: Heating method
[0384] Starting temperature: 50℃
[0385] Reach temperature: 200℃
[0386] Measuring interval: 1.0℃
[0387] Heating rate: 4.0℃ / min
[0388] Piston cross-sectional area: 1.000cm 2
[0389] Test load (piston load): 10.0kgf (0.9807MPa)
[0390] Warm-up time: 300 seconds
[0391] Die hole diameter: 1.0mm
[0392] Mold length: 1.0mm
[0393] <Measurement of Glass Transition Temperature (Tg) of Amorphous Resin Different from Polymer A>
[0394] The glass transition temperature (Tg) is measured by using a differential scanning calorimeter "Q2000" (manufactured by TA Instruments) in accordance with ASTM D3418-82.
[0395] The melting points of indium and zinc are used for temperature correction of the detection unit of the device, and the melting heat of indium is used for heat correction.
[0396] Specifically, by accurately weighing 3 mg of a sample, placing the sample in an aluminum pan, and using an empty aluminum pan as a reference, measurement was performed under the following conditions.
[0397] Heating rate: 10℃ / min
[0398] Measurement start temperature: 30°C
[0399] Measurement end temperature: 180℃
[0400] In the measurement, the temperature was raised to 180°C and maintained for 10 minutes, then the temperature was lowered to 30°C at a temperature drop rate of 10°C / min, and then the temperature was raised again. During the second temperature rise, the change in specific heat was obtained in the temperature range of 30°C to 100°C. The intersection of the line at the midpoint between the baselines before and after the specific heat change at this time and the differential thermal curve was taken as the glass transition temperature (Tg).
[0401] Furthermore, the temperature at the maximum endothermic peak of the temperature-endothermic quantity curve in the temperature range of 60° C. to 90° C. was taken as the melting peak temperature (Tp) of the polymer melting point.
[0402] (Separation of Polymer A and Binder Resin from Toner)
[0403] Similar to the above method, after the polymer A and the binder resin are separated from the toner by utilizing the difference in solubility in the solvent, the DSC measurement is performed.
[0404] <Method for measuring acid value (Av) of polymer A and amorphous resin different from polymer A>
[0405] The acid value is the number of milligrams of potassium hydroxide required to neutralize acid components contained in 1 g of a sample such as free fatty acids, resin acids, etc. The acid value is measured in accordance with JIS K 0070-1992.
[0406] (1) Reagents
[0407] A total of 1.0 g of phenolphthalein was dissolved in 90 mL of ethanol (95% by volume), and ion-exchanged water was added to make 100 ml to obtain a phenolphthalein solution.
[0408] The special grade potassium hydroxide amounting to 7g is dissolved in the water of 5mL, and ethanol (95 volume %) is added to obtain 1L. The solution is put into an alkali-resistant container and allowed to stand for 3 days, while avoiding contact with carbon dioxide gas etc., filtered subsequently, and potassium hydroxide solution is obtained. The potassium hydroxide solution obtained is kept in an alkali-resistant container. The hydrochloric acid of 0.1mol / L amounting to 25mL is put into a conical flask, a few drops of phenolphthalein solution are added thereto, potassium hydroxide solution is used to titrate, and the factor of potassium hydroxide solution is determined by the amount of potassium hydroxide solution required for neutralization. Use the 0.1mol / L hydrochloric acid prepared according to JIS K 8001-1998.
[0409] (2) Operation
[0410] (A) Main Tests
[0411] A total of 2.0 g of the pulverized sample was accurately weighed and placed in a 200 mL conical flask, 100 mL of a mixed solution of toluene / ethanol (2:1) was added, and dissolved for 5 hours. Then, a few drops of phenolphthalein solution were added as an indicator, and titrated using potassium hydroxide solution. The endpoint of the titration was assumed to be when the light red color of the indicator lasted for about 30 seconds.
[0412] (B) Blank test
[0413] Titration was performed in the same manner as described above, except that no sample was used (ie, only a mixed solution of toluene / ethanol (2:1) was used).
[0414] (3) The obtained result was substituted into the following equation to calculate the acid value.
[0415] A=[(CB)×f×5.61] / S
[0416] Here, A: acid value (mgKOH / g); B: amount of potassium hydroxide solution added in the blank test (mL); C: amount of potassium hydroxide solution added in the main test (mL); f: factor of potassium hydroxide solution; S: mass of sample (g).
[0417] <Method for measuring weight average particle size (D4) of toner>
[0418] The weight average particle size (D4) of the toner is calculated in the following manner. A precision particle size distribution measuring device (registered trademark, "Coulter Counter Multisizer 3", manufactured by Beckman Coulter, Inc.) based on the pore resistance method and equipped with a nozzle having a diameter of 100 μm is used as a measuring device. The dedicated software "Beckman Coulter Multisizer 3 Version 3.51" (manufactured by Beckman Coulter, Inc.) equipped with the device is used to set the measurement conditions and analyze the measurement data. The measurement is performed with 25,000 effective measurement channels.
[0419] A solution prepared by dissolving special grade sodium chloride in ion exchange water to a concentration of about 1 mass %, such as "ISOTON II" manufactured by Beckman Coulter, Inc., can be used as the aqueous electrolyte solution used for measurement.
[0420] Prior to measurement and analysis, the dedicated software was set in the following manner.
[0421] On the "Change Standard Observation Method (SOM)" screen of the dedicated software, the total count of the control mode was set to 50,000 particles, the number of measurements was set to 1, and the value obtained using "Standard Particles 10.0 μm" (manufactured by Beckman Coulter, Inc.) was set as the Kd value. The threshold and noise level were automatically set by pressing the "Threshold / Noise Level Measurement" button. In addition, the current was set to 1600 μA, the gain was set to 2, the electrolyte solution was set to ISOTON II, and "Rinse the mouth tube after measurement" was checked.
[0422] On the "Pulse to Size Conversion Settings" screen of the dedicated software, set the element interval to logarithmic size, set the size element to 256 size elements, and set the size range to 2 μm to 60 μm.
[0423] The specific measurement method is described below.
[0424] (1) Pour about 200 ml of electrolyte aqueous solution into a 250 ml glass round-bottom beaker dedicated to Multisizer 3, place the beaker on the sample stage, and stir it counterclockwise at 24 rpm with a stirring rod. Remove contaminants and bubbles in the orifice tube using the "pore flushing" function of the dedicated software.
[0425] (2) A total of about 30 ml of the electrolyte aqueous solution was placed in a 100 ml glass flat-bottom beaker. Then, about 0.3 ml of a dilution of "Contaminon N" (a 10% by mass aqueous solution of a neutral detergent for washing precision measuring devices at pH 7, composed of a nonionic surfactant, an anionic surfactant and an organic builder, manufactured by Wako Pure Chemical Industries, Ltd.) diluted 3 times by mass with ion exchange water was added thereto as a dispersant.
[0426] (3) An ultrasonic disperser "Ultrasonic Dispersion System Tetora 150" (manufactured by Nikkaki Bios Co., Ltd.) with a power output of 120 W in which two vibrators with an oscillation frequency of 50 kHz were installed to have a phase shift of 180 degrees was prepared. A total of 3.3 L of ion-exchanged water was put into the water tank of the ultrasonic disperser, and about 2 mL of CONTAMINON N was added to the water tank.
[0427] (4) The beaker of (2) above is set in the beaker fixing hole of the ultrasonic disperser, and the ultrasonic disperser is operated. Then, the height position of the beaker is adjusted so that the resonance state of the liquid surface of the aqueous electrolyte solution in the beaker is maximized.
[0428] (5) While the electrolyte aqueous solution in the beaker of (4) is irradiated with ultrasonic waves, a total of 10 mg of toner particles are gradually added to the electrolyte aqueous solution and dispersed therein. Then, the ultrasonic dispersion treatment is continued for another 60 seconds. During the ultrasonic dispersion, the water temperature in the water tank is appropriately adjusted to 10° C. to 40° C.
[0429] (6) The electrolyte aqueous solution of (5) above in which the toner particles are dispersed is dropped into the round-bottom beaker of (1) above which has been set in the sample stage using a pipette, and the measurement concentration is adjusted to about 5%. Then, measurement is performed until the number of measured particles reaches 50,000.
[0430] (7) Use the dedicated software provided with the device to analyze the measurement data and calculate the weight average particle size (D4). When the dedicated software is set to graph / volume %, the "average diameter" on the "analysis / volume statistics (arithmetic mean)" interface is the weight average particle size (D4).
[0431] <Method for measuring average circularity of toner>
[0432] The average circularity of the toner is measured using a flow-type particle image analyzer "FPIA-3000" (manufactured by Sysmex Corporation) under the measurement and analysis conditions at the time of calibration.
[0433] The measuring principle of the flow-type particle image analyzer "FPIA-3000" (manufactured by Sysmex Corporation) is to capture a still image as an image of flowing particles and perform image analysis. The sample added to the sample chamber is fed into the flat sheath flow cell by a sample suction syringe. The sample fed into the flat sheath flow cell is sandwiched in the middle by the sheath liquid to form a flat flow. The sample passing through the flat sheath flow cell is irradiated with a strobe light at intervals of 1 / 60 seconds, which enables the image of the flowing particles to be captured as a still image. In addition, because the flow is flattened, the image is captured in a focused form. The particle image is captured with a CCD camera, and the captured image is image processed with an image processing resolution of 512×512 pixels (0.37μm×0.37μm per pixel), and the contour of each particle image is extracted, and the projected area S, perimeter L, etc. of the particle image are measured.
[0434] Next, the circle equivalent diameter and circularity are determined using the area S and the circumference L. The circle equivalent diameter is the diameter of a circle having the same area as the projected area of the particle image, and the circularity C is determined as a value obtained by dividing the circumference of the circle determined by the circle equivalent diameter by the circumference of the particle projected image. The circularity is calculated by the following formula.
[0435] Circularity C = 2 × (π × S) 1 / 2 / L
[0436] When the particle image is circular, the circularity is 1.000, and as the unevenness on the circumference of the particle image increases, the circularity becomes smaller. After calculating the circularity of each particle, the circularity range of 0.200 to 1.000 is divided by 800, the arithmetic mean of the obtained circularity is calculated, and this value is defined as the average circularity.
[0437] The specific measurement method is described below.
[0438] First, about 20 mL of ion exchange water from which solid impurities had been removed in advance was placed in a glass container. About 0.2 ml of a dilution prepared by diluting "Contaminon N (a 10% by mass aqueous solution of a neutral detergent for washing precision measuring devices having a pH of 7, composed of a nonionic surfactant, an anionic surfactant and an organic builder, manufactured by Wako Pure Chemical Industries, Ltd.) with about 3 times the mass of ion exchange water was added thereto as a dispersant.
[0439] In addition, about 0.02 g of the measurement sample was added and dispersed for 2 minutes using an ultrasonic disperser to obtain a dispersion liquid for measurement. At this time, the dispersion liquid was appropriately cooled to a temperature of 10° C. to 40° C. A desktop ultrasonic cleaning disperser ("VS-150" (manufactured by Velvo-Clear Co.) with an oscillation frequency of 50 kHz and an electrical output of 150 W was used as an ultrasonic disperser, a predetermined amount of ion exchange water was placed in a water tank and about 2 mL of CONTAMINON N was added to the water tank.
[0440] A flow type particle image analyzer equipped with a standard objective lens (×10) was used, and Particle Sheath "PSE-900A" (manufactured by Sysmex Corporation) was used as a sheath liquid for measurement. The dispersion prepared according to the procedure was introduced into the flow type particle image analyzer, and 3000 toner particles were measured in the HPF measurement mode and the total count mode.
[0441] Then, the binarization threshold value in the particle analysis was set to 85%, and the particle size to be analyzed was set to a circle equivalent diameter of 1.98 μm to 39.96 μm, and the average circularity of the toner was obtained.
[0442] In the measurement, automatic focusing is performed before the start of measurement using standard latex particles (for example, "Research and Test Particles Latex Microsphere Suspensions 5200A" manufactured by Duke Scientific Inc., diluted with ion-exchanged water). Then, focusing is preferably performed every 2 hours from the start of measurement.
[0443] <Method for measuring 50% particle diameter (D50) based on volume distribution of polymer fine particles, amorphous resin fine particles other than polymer A, aliphatic hydrocarbon compound fine particles, and colorant fine particles>
[0444] A dynamic light scattering type particle size distribution meter NANOTRAC UPA-EX150 (manufactured by Nikkiso Co., Ltd.) is used to measure the 50% particle diameter (D50) based on volume distribution of polymer fine particles, amorphous resin fine particles other than polymer A, aliphatic hydrocarbon compound fine particles, and colorant fine particles. Specifically, the measurement is performed according to the following procedure.
[0445] In order to prevent aggregation of the measurement sample, the dispersion in which the measurement sample is dispersed is introduced into an aqueous solution including FAMILYFRESH (manufactured by Kao Corporation) and stirred. After stirring, the measurement sample is injected into the above device, two measurements are performed, and the average value is determined.
[0446] As measurement conditions, the measurement time is 30 seconds, the refractive index of the sample particles is 1.49, the dispersion medium is water, and the refractive index of the dispersion medium is 1.33.
[0447] The volume particle size distribution of the measurement sample is measured, and the particle size at which the cumulative volume is 50% on the small particle size side in the cumulative volume distribution from the measurement result is taken as the 50% particle size (D50) based on the volume distribution of each particle.
[0448] <Method for measuring complex viscosity of toner>
[0449] A rotating plate type rheometer "ARES" (manufactured by TAINSTRUMENTS) was used as a measuring apparatus.
[0450] A sample obtained by pressure-molding the toner into a disk shape having a diameter of 25 mm and a thickness of 2.0±0.3 mm under an environment of 25° C. using a sheet molding machine is used as a measurement sample.
[0451] The sample is mounted on parallel plates, and the temperature is raised from room temperature (25°C) to 110°C within 15 minutes to adjust the shape of the sample, and then cooled to the measurement start temperature of viscoelasticity. Then, the measurement is started to measure the complex viscosity. At this time, the measurement sample is set so that the initial normal force becomes zero. In addition, in subsequent measurements, the influence of the normal force can be eliminated by performing automatic stretching adjustment (automatic stretching adjustment ON) as described below.
[0452] The measurement was performed under the following conditions.
[0453] (1) Use a parallel plate with a diameter of 25 mm.
[0454] (2) Set the frequency to 6.28 rad / sec (1.0 Hz).
[0455] (3) The initial value of the applied strain (strain) was set to 1.0%.
[0456] (4) The measurement was performed at a heating rate of 2.0° C. / min between 40° C. and 100° C. In the measurement, the following setting conditions of the automatic adjustment mode were used. The measurement was performed in the automatic strain adjustment mode (Auto Strain).
[0457] (5) The maximum applied strain was set to 40.0%.
[0458] (6) The maximum allowable torque is set to 150.0 g·cm, and the minimum allowable torque is set to 0.2 g·cm.
[0459] (7) The strain adjustment is set to 20.0% of the current strain. During the measurement, the automatic tension adjustment mode (AutoTension) is used.
[0460] (8) The automatic stretching direction is set to compression.
[0461] (9) The initial static force was set to 10.0 g and the automatic stretch sensitivity was set to 40.0 g.
[0462] (10) As the operating condition of automatic stretching, the sample modulus is 1.0×10 3 Pa or above.
[0463] Example
[0464] Hereinafter, the present invention will be specifically described by way of Examples, but these do not limit the present invention at all. In the following formulations, parts are by mass unless otherwise specified.
[0465] <Preparation Example of Polymer A1>
[0466] -Solvent: 100.0 parts of toluene
[0467] -Monomer composition 100.0 parts
[0468] (Assume that the monomer composition is obtained by mixing the following behenyl acrylate, methacrylonitrile and styrene in the ratio shown below)
[0469] -Behenyl acrylate (first polymerizable monomer) 67.0 parts (28.9 mol%)
[0470] -Methacrylonitrile (second polymerizable monomer) 22.0 parts (53.8 mol%)
[0471] -Styrene (third polymerizable monomer) 11.0 parts (17.3 mol%)
[0472] -Polymerization initiator: tert-butyl peroxypivalate (manufactured by NOF Corporation: PERBUTYL PV) 0.5 parts
[0473] The above materials were put into a reaction vessel equipped with a reflux condenser, a stirrer, a thermometer and a nitrogen inlet tube under a nitrogen atmosphere. The materials were heated to 70°C in the reaction vessel and subjected to polymerization reaction for 12 hours under stirring at 200rpm to obtain a solution in which the polymer of the monomer composition was dissolved in toluene. Subsequently, the temperature of the solution was lowered to 25°C, and then the solution was added to 1000.0 parts of methanol under stirring to precipitate methanol insolubles. The obtained methanol insolubles were separated by filtration, further washed with methanol, and vacuum dried at 40°C for 24 hours to obtain polymer A1. The weight average molecular weight of polymer A1 was 68,400, the melting point was 62°C, and the acid value was 0.0 mg KOH / g.
[0474] Polymer A1 was analyzed by NMR and found to include 28.9 mol% of monomer units derived from behenyl acrylate, 53.8 mol% of monomer units derived from methacrylonitrile, and 17.3 mol% of monomer units derived from styrene. The SP values of the polymerizable monomer and the unit derived from the polymerizable monomer were calculated by the above method.
[0475] <Preparation of Monomer Having a Carbamate Group>
[0476] A total of 50.0 parts of methanol was put into a reaction container. Then, 5.0 parts of KARENZMOI [2-isocyanatoethyl methacrylate] (Showa Denko KK) was added dropwise at 40° C. under stirring. After the dropwise addition was completed, stirring was performed for 2 hours while maintaining 40° C. Then, unreacted methanol was removed by an evaporator to prepare a monomer having a carbamate group.
[0477] <Preparation of Monomer Having Urea Group>
[0478] A total of 50.0 parts of dibutylamine was added to the reaction container. Then, 5.0 parts of KARENZMOI [2-isocyanatoethyl methacrylate] (Showa Denko KK) was added dropwise at room temperature under stirring. After the addition was completed, stirring was performed for 2 hours. Then, unreacted dibutylamine was removed by an evaporator to prepare a monomer having a urea group.
[0479] <Preparation Example of Polymers A2 to A30>
[0480] Polymers A2 to A30 were obtained by carrying out the reaction in the same manner as in the Preparation Example of Polymer A1 except that the polymerizable monomers and the parts were changed as shown in Table 1. The physical properties of Polymers A1 to A30 are shown in Tables 2 to 4.
[0481] [Table 1]
[0482]
[0483] The abbreviations of Tables 1 to 4 are as follows.
[0484] BEA: Behenyl acrylate
[0485] BMA: Behenyl Methacrylate
[0486] SA: Stearyl acrylate
[0487] MYA: Triacontyl acrylate
[0488] OA: Dioctadecyl acrylate
[0489] HA: Hexadecyl acrylate
[0490] MN: Methacrylonitrile
[0491] AN: Acrylonitrile
[0492] HPMA: 2-Hydroxypropyl Methacrylate
[0493] AM: Acrylamide
[0494] UT: Monomer with urethane group
[0495] UR: Monomer with urea group
[0496] AA: Acrylic acid
[0497] VA: Vinyl Acetate
[0498] MA: Methyl acrylate
[0499] St:Styrene
[0500] MM: Methyl methacrylate
[0501] [Table 2]
[0502]
[0503] [Table 3]
[0504]
[0505] [Table 4]
[0506]
[0507] <Preparation Example of Amorphous Resin 1 Different from Polymer A>
[0508] -Solvent: 100.0 parts of xylene
[0509] -95.0 parts of styrene
[0510] - n-Butyl acrylate 5.0 parts
[0511] -Polymerization initiator tert-butyl peroxypivalate (manufactured by NOF Corporation: PERBUTYLPV) 0.5 parts
[0512] The above materials were put into a reaction vessel equipped with a reflux condenser, a stirrer, a thermometer and a nitrogen inlet tube under a nitrogen atmosphere. The materials were heated to 185° C. in the reaction vessel and subjected to polymerization reaction for 10 hours under stirring at 200 rpm. Subsequently, the solvent was removed and vacuum dried at 40° C. for 24 hours to obtain an amorphous resin 1 different from polymer A. The amorphous resin 1 different from polymer A had a weight average molecular weight of 3500, a softening point of 96° C., a glass transition temperature Tg of 58° C., and an acid value of 0.0 mg KOH / g.
[0513] <Preparation Example of Dispersion Liquid of Polymer Fine Particles 1>
[0514] -Toluene (Wako Pure Chemical Industries) 300 parts
[0515] -Polymer A1 100 parts
[0516] The above materials were weighed, mixed and dissolved at 90°C.
[0517] Separately, 5.0 parts of sodium dodecylbenzenesulfonate and 10.0 parts of sodium laurate were added to 700 parts of ion-exchanged water, and the components were heated and dissolved at 90°C.
[0518] Then, by using ultra-high speed stirring device TKROBOMIX (manufactured by PRIMIX Corporation), the toluene solution and the aqueous solution were mixed and stirred at 7000rpm. Then, by using high pressure impact type dispersion machine NANOMIZER (manufactured by Yoshida Kikai Co., Ltd.), the mixture was emulsified under a pressure of 200MPa. Then, toluene was removed using an evaporator, and the concentration was adjusted with ion exchange water to obtain an aqueous dispersion having a concentration of 20% by mass of polymer fine particles 1 (dispersion of polymer fine particles 1).
[0519] The 50% particle diameter (D50) based on volume distribution of the polymer fine particles 1 was measured using a dynamic light scattering type particle size distribution meter NANOTRAC UPA-EX150 (manufactured by Nikkiso Co., Ltd.) and found to be 0.40 μm.
[0520] <Preparation Example of Dispersion Liquid of Polymer Fine Particles 2 to 30>
[0521] Emulsification was performed in the same manner as in the preparation example of the dispersion of polymer fine particles 1, except that polymer A was changed as shown in Table 5, to obtain dispersions of polymer fine particles 2 to 30. The physical properties of the dispersions of polymer fine particles 1 to 30 are shown in Table 5.
[0522] [Table 5]
[0523]
[0524] <Preparation Example of Dispersion Liquid of Amorphous Resin Fine Particles 1 Different from Polymer A>
[0525] -Tetrahydrofuran (manufactured by Wako Pure Chemical Industries, Ltd.) 300 parts
[0526] - Amorphous resin 1 100 parts other than polymer A
[0527] - Anionic surfactant NEOGEN RK (manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) 0.5 parts
[0528] The above materials were weighed, mixed and dissolved.
[0529] Then, 20.0 parts of 1 mol / L ammonia water was added, and the components were stirred at 4000 rpm by using an ultra-high speed stirring device TKROBOMIX (manufactured by PRIMIX Corporation). Then, a total of 700 parts of ion exchange water were added at a rate of 8 g / min to precipitate amorphous resin fine particles different from polymer A. Then, tetrahydrofuran was removed using an evaporator, and the concentration was adjusted with ion exchange water to obtain an aqueous dispersion having a concentration of 20% by mass of amorphous resin fine particles 1 different from polymer A (dispersion of amorphous resin fine particles 1).
[0530] The 50% particle diameter (D50) based on volume distribution of the amorphous resin fine particles 1 other than the polymer A was 0.13 μm.
[0531] <Preparation Example of Release Agent (Aliphatic Hydrocarbon Compound) Fine Particle Dispersion>
[0532] - Aliphatic hydrocarbon compound HNP-51 (manufactured by Nippon Seiro Co., Ltd.) 100 parts - Anionic surfactant NEOGEN RK (manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) 5 parts
[0533] - 395 parts of ion exchange water
[0534] The above materials were weighed, put into a mixing container equipped with a stirrer, heated to 90° C., circulated to CLEARMIXW MOTION (manufactured by M Technique Co., Ltd.) and dispersed for 60 minutes. The conditions for the dispersion treatment were as follows.
[0535] -Rotor outer diameter: 3cm
[0536] - Clearance: 0.3mm
[0537] - Rotor speed: 19,000r / min
[0538] -Screen speed: 19,000r / min
[0539] After the dispersion treatment, the mixture is cooled to 40°C under the cooling treatment conditions of a rotor speed of 1000 r / min, a sieve speed of 0 r / min and a cooling rate of 10°C / min to obtain an aqueous dispersion (release agent (aliphatic hydrocarbon compound) fine particle dispersion) with a release agent (aliphatic hydrocarbon compound) fine particle concentration of 20% by mass.
[0540] The 50% particle diameter (D50) based on volume distribution of fine particles of the releasing agent (aliphatic hydrocarbon compound) was measured using a dynamic light scattering type particle size distribution meter NANOTRAC UPA-EX150 (manufactured by Nikkiso Co., Ltd.) and found to be 0.15 μm.
[0541] <Preparation of Colorant Fine Particle Dispersion Liquid>
[0542] - Colorant 50.0 parts (cyan pigment: pigment blue 15:3 manufactured by Dainichiseika Color & Chemicals Mfg. Co., Ltd.)
[0543] - Anionic surfactant NEOGEN RK (manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) 7.5 parts
[0544] - 442.5 parts of ion exchange water
[0545] The above materials are weighed and mixed, dissolved, and dispersed for about 1 hour using a high-pressure impact type disperser NANOMIZER (manufactured by Yoshida Kikai Co., Ltd.) to obtain an aqueous dispersion (colorant-fine particle dispersion) in which the colorant is dispersed and the concentration of the colorant fine particles is 10 mass%.
[0546] The 50% particle diameter (D50) based on volume distribution of the colorant fine particles was measured using a dynamic light scattering type particle size distribution meter NANOTRAC UPA-EX150 (manufactured by Nikkiso Co., Ltd.) and found to be 0.20 μm.
[0547] <Preparation Example of Toner 1>
[0548] - 500 parts of dispersion of polymer fine particles 1
[0549] - Release agent (aliphatic hydrocarbon compound fine particle dispersion) 50 parts
[0550] - 80 parts of colorant fine particle dispersion
[0551] - 160 parts of ion exchange water
[0552] The materials were put into a round stainless steel flask and mixed, and then 10 parts of a 10% magnesium sulfate aqueous solution were added. Subsequently, dispersion was performed at 5000 r / min for 10 minutes by using a homogenizer ULTRA-TURRAX T50 (manufactured by IKA). Then, the mixture was heated to 58° C. in a heated water bath while using a stirring blade and appropriately adjusting the rotation speed to stir the mixture.
[0553] The volume average particle size of the formed aggregated particles was appropriately confirmed using Coulter Multisizer III, and when aggregated particles with a volume average particle size of about 6.00 μm were formed, 100 parts of sodium ethylenediaminetetraacetate were added, and then heated to 75° C. while continuing to stir. Then, the aggregated particles were melted by keeping at 75° C. for 1 hour.
[0554] Then, the mixture was cooled to 50°C and maintained for 3 hours to promote crystallization of the polymer.
[0555] Thereafter, washing with a 5% sodium ethylenediaminetetraacetate aqueous solution was performed while maintaining the temperature at 50°C, thereby performing a step of removing polyvalent metal ions derived from the flocculant.
[0556] Then, the mixture was cooled to 25° C., filtered and solid-liquid separated, and then washed with ion-exchanged water. After washing, the mixture was dried using a vacuum dryer to obtain toner particles 1 having a weight average particle size (D4) of about 6.07 μm.
[0557] -Toner particles 1 100 parts
[0558] - 3 parts of large-diameter silica fine particles (average particle size 130 nm) surface-treated with hexamethyldisilazane
[0559] - 1 part of small-diameter silica fine particles (average particle size 20 nm) surface-treated with hexamethyldisilazane
[0560] The mixture was stirred for 30 s by using a Henschel mixer FM-10C (manufactured by Nippon Coke & Engineering Co., Ltd.). -1 The above materials were mixed at a rotation speed of 0.020 rpm and a rotation time of 10 minutes to obtain Toner 1. The constituent materials of Toner 1 are shown in Table 6.
[0561] The weight average particle diameter (D4) of Toner 1 was 6.1 μm, and the average circularity was 0.975. The physical properties of Toner 1 are shown in Table 7.
[0562] [Table 6]
[0563]
[0564] The abbreviations in Table 6 are as follows.
[0565] Mg: magnesium sulfate
[0566] Ca: Calcium nitrate
[0567] Zn: Zinc chloride
[0568] Al: Aluminum sulfate
[0569] Na: Sodium EDTA
[0570] Li: Lithium citrate
[0571] K: Potassium citrate
[0572] [Table 7]
[0573]
[0574] *1: "Metal domain diameter" in the table indicates the domain diameter of at least one of a polyvalent metal and a monovalent metal.
[0575] <Preparation Examples of Toners 2 to 32 and 34 to 44>
[0576] Toners 2 to 32 and 34 to 44 were obtained by performing the same operation as in the Preparation Example of Toner 1, except that the type and amount of the dispersion liquid of polymer fine particles 1, the amount of amorphous resin fine particles 1 other than polymer A, the type and addition amount of the flocculant, the type of the remover, and the addition temperature of the remover in the Preparation Example of Toner 1 were changed as shown in Table 6. The physical properties are shown in Table 7.
[0577] <Preparation Example of Toner 33>
[0578] -Polymer A1 100.0 parts
[0579] - Aliphatic hydrocarbon compound HNP-51 (manufactured by Nippon Seiro Co., Ltd.) 10.0 parts
[0580] - Colorant 8.0 parts (cyan pigment: pigment blue 15:3 manufactured by Dainichiseika Color & Chemicals Mfg. Co., Ltd.)
[0581] -3,5-di-tert-butyl salicylate aluminum compound 0.03 parts
[0582] The mixture was stirred for 20 s using a Henschel mixer (Model FM-75, manufactured by Mitsui Mining Co., Ltd.). -1 The above materials were mixed at a rotation speed of 0.05 and a rotation time of 5 minutes, and then melt-kneaded using a biaxial kneader (PCM-30, manufactured by Ikegai Co., Ltd.) with a set temperature of 130°C.
[0583] The obtained kneaded product was cooled and coarsely pulverized to 1 mm or less with a hammer mill to obtain a coarsely pulverized product.
[0584] The obtained roughly pulverized product was finely pulverized with a mechanical pulverizer (T-250, manufactured by Turbo Kogyo Co., Ltd.).
[0585] Furthermore, classification was performed using FACULTY F-300 (manufactured by Hosokawa Micron Corporation) to obtain toner particles 33 having a weight average particle size (D4) of about 6.07 μm. The operating conditions were a classification rotor rotation speed of 130 s -1 , the dispersion rotor speed is 120s -1 .
[0586] -Toner particles 33 100 parts
[0587] - 3 parts of large-diameter silica fine particles (average particle size 130 nm) surface-treated with hexamethyldisilazane
[0588] - 1 part of small-diameter silica fine particles (average particle size 20 nm) surface-treated with hexamethyldisilazane
[0589] The mixture was stirred for 30 s by using a Henschel mixer FM-10C (manufactured by Nippon Coke & Engineering Co., Ltd.). -1 The above materials were mixed at a rotation speed of 0.000 and a rotation time of 10 minutes to obtain Toner 33. The weight average particle size (D4) of Toner 33 was 6.1 μm, and the average circularity was 0.975. The physical properties of Toner 33 are shown in Table 7.
[0590] <Preparation Example of Magnetic Carrier 1>
[0591] - The magnetization intensity of the magnet 1 (1000 / 4π (kA / m)) with a number average particle size of 0.30 μm under a magnetic field is 65 Am 2 / kg)
[0592] - The magnetization intensity of the magnet 2 (1000 / 4π (kA / m)) with a number average particle size of 0.50 μm under a magnetic field is 65 Am 2 / kg)
[0593] A total of 4.0 parts of a silane compound (3-(2-aminoethylaminopropyl)trimethoxysilane) was added to 100 parts of each of the above materials, and mixed and stirred at high speed in a container at 100° C. or higher to treat each fine particle.
[0594] - Phenol: 10% by mass
[0595] -Formaldehyde solution: 6% by mass
[0596] (40% by mass formaldehyde, 10% by mass methanol, 50% by mass water)
[0597] - Magnet body 1 treated with the above silane compound: 58% by mass
[0598] - Magnet 2 treated with the above silane compound: 26% by mass
[0599] A total of 100 parts of the above materials, 5 parts of a 28 mass % ammonia aqueous solution and 20 parts of water were put into a flask, heated to 85° C. over 30 minutes while stirring and mixing, and maintained for 3 hours to cause a polymerization reaction and cure the produced phenolic resin.
[0600] Thereafter, the solidified phenolic resin was cooled to 30°C, water was further added, the supernatant was removed, the precipitate was washed with water, and then air-dried. Subsequently, the obtained product was dried at a temperature of 60°C and under reduced pressure (5 mmHg or less) to obtain a magnetic substance dispersed spherical magnetic carrier 1. The 50% particle size (D50) based on volume was 34.21 μm.
[0601] <Preparation Example of Two-Component Developer 1>
[0602] A total of 92.0 parts of the magnetic carrier 1 and 8.0 parts of the toner 1 were mixed using a V-type mixer (V-20, manufactured by Seishin Enterprise Co., Ltd.) to obtain a two-component developer 1.
[0603] <Preparation Example of Two-Component Developers 2 to 44>
[0604] Two-component developers 2 to 44 were obtained by carrying out the same operation as in the preparation example of the two-component developer 1 except that changes as shown in Table 8 were made.
[0605] [Table 8]
[0606] Two-component developer Toner Magnetic carrier Example 1 1 1 1 Example 2 2 2 1 Example 3 3 3 1 Example 4 4 4 1 Example 5 5 5 1 Example 6 6 6 1 Example 7 7 7 1 Example 8 8 8 1 Example 9 9 9 1 Example 10 10 10 1 Embodiment 11 11 11 1 Example 12 12 12 1 Example 13 13 13 1 Embodiment 14 14 14 1 Embodiment 15 15 15 1 Example 16 16 16 1 Embodiment 17 17 17 1 Embodiment 18 18 18 1 Embodiment 19 19 19 1 Embodiment 20 20 20 1 Embodiment 21 21 21 1 Embodiment 22 22 22 1 Embodiment 23 23 23 1 Embodiment 24 24 24 1 Embodiment 25 25 25 1 Embodiment 26 26 26 1 Embodiment 27 27 27 1 Embodiment 28 28 28 1 Embodiment 29 29 29 1 Embodiment 30 30 30 1 Embodiment 31 31 31 1 Embodiment 32 32 32 1 Embodiment 33 33 33 1 Embodiment 34 41 41 1 Comparative Example 1 34 34 1 Comparative Example 2 35 35 1 Comparative Example 3 36 36 1 Comparative Example 4 37 37 1 Comparative Example 5 38 38 1 Comparative Example 6 39 39 1 Comparative Example 7 40 40 1 Comparative Example 8 42 42 1 Comparative Example 9 43 43 1 Comparative Example 10 44 44 1
[0607] <Example 1>
[0608] Evaluation was performed using the two-component developer 1 described above.
[0609] A modified printer imageRUNNERADVANCE C5560 manufactured by Canon Inc. for digital commercial printing was used as an image forming apparatus, and a two-component developer 1 was placed in the developing device at the cyan position. The modification of the apparatus included the ability to freely set the fixing temperature of the developer bearing member, the process speed, the DC voltage VDC, the charging voltage VD of the electrostatic latent image bearing member, and the change of the laser power. In the image output evaluation, an FFh image (solid image) of a desired image ratio was output, and V was adjusted. DC 、V D and laser power were adjusted so as to obtain a desired toner loading amount on a FFh image on paper, and the following evaluation was performed.
[0610] FFh is a value obtained by hexadecimal representation of 256 gray levels, 00h is the first gray level of the 256 gray levels (white area), and FFh is the 256 gray level of the 256 gray levels (solid part).
[0611] The evaluation was based on the following evaluation method, and the results are shown in Table 9.
[0612] [Developing performance]
[0613] Paper: CS-680(68.0g / m 2 )
[0614] (Sold by Canon Marketing Japan Co., Ltd.)
[0615] Toner loading on paper: 0.35 mg / cm 2 (FFh image)
[0616] (The DC voltage V DC , the charging voltage V of the electrostatic latent image bearing member D and laser power regulation)
[0617] Evaluation image: Ruled line pattern with an image ratio of 5% on the entire surface of A4 paper
[0618] Test environment: High temperature and high humidity environment (temperature 30°C / humidity 80% RH (hereinafter H / H))
[0619] Processing speed: 377mm / sec
[0620] A total of 100,000 print evaluation images were output, and the developing performance was evaluated. When developing streaks appeared, longitudinal streaky stains appeared on the paper. Visual evaluation of the use state was used as an evaluation index for developing performance. In the case of evaluations of A to D, it was determined that the effect of the present invention was obtained.
[0621] A: No vertical streaks on the paper
[0622] B: 1 or 2 vertical stripes on the paper
[0623] C: 3 or 4 vertical stripes on the paper
[0624] D: 5 or 6 vertical stripes on the paper
[0625] E: More than 7 vertical stripes on the paper
[0626] [Low temperature fixability]
[0627] Paper: GFC-081(81.0g / m 2 )
[0628] (Sold by Canon Marketing Japan Co., Ltd.)
[0629] Toner loading on paper: 0.50 mg / cm 2
[0630] (The DC voltage V DC , the charging voltage V of the electrostatic latent image bearing member D and laser power regulation)
[0631] Evaluation image: 2cm×5cm image located in the center of A4 paper
[0632] Test environment: Low temperature and low humidity environment: temperature 15°C / humidity 10% RH (hereinafter "L / L")
[0633] Fixing temperature: 150℃
[0634] Processing speed: 377mm / sec
[0635] Evaluation images were output to evaluate low-temperature fixability. The value of the image density reduction rate was used as an evaluation index for low-temperature fixability.
[0636] First, the image density reduction rate was determined by measuring the image density at the center using an X-Rite color reflection densitometer (500 series: manufactured by X-Rite Co., Ltd.). Next, 4.9 kPa (50 g / cm 2 ) was applied to the portion where the image density had been measured, the fixed image was rubbed with Silbon paper (five reciprocations), and the image density was measured again.
[0637] Then, the reduction rate of the image density before and after rubbing was calculated using the following equation. The obtained image density reduction rate was evaluated according to the following evaluation criteria. In the case of evaluation A to D, it was determined that the effect of the present invention was obtained.
[0638] Image density reduction rate = [(image density before rubbing) - (image density after rubbing)] / (image density before rubbing) × 100
[0639] (Evaluation Criteria)
[0640] A: Image density reduction rate is less than 3%
[0641] B: Image density reduction rate is 3% or more and less than 5%
[0642] C: Image density reduction rate is 5% or more and less than 8%
[0643] D: Image density reduction rate is 8% or more and less than 13%
[0644] E: Image density reduction rate is 13% or more
[0645] [Charge retention rate under high temperature and high humidity environment]
[0646] Paper: GFC-081(81.0g / m 2 )(Canon Marketing Japan Co.,Ltd.)
[0647] Toner loading on paper: 0.35 mg / cm 2
[0648] (The DC voltage V DC , the charging voltage V of the electrostatic latent image bearing member D and laser power regulation)
[0649] Evaluation image: 2cm×5cm image located in the center of A4 paper
[0650] Fixing test environment: High temperature and high humidity environment: temperature 30°C / humidity 80% RH (hereinafter "H / H")
[0651] Processing speed: 377mm / sec
[0652] The toner on the electrostatic latent image bearing member is sucked and collected using a metal cylindrical pipe and a cylindrical filter to calculate the triboelectric charge amount of the toner. Specifically, the triboelectric charge amount of the toner on the electrostatic latent image bearing member is measured by a Faraday cage.
[0653] The Faraday cage is a coaxial double cylinder in which the inner cylinder and the outer cylinder are insulated from each other. When a charged body with a charge amount Q is inserted into the inner cylinder, it seems that there is a metal cylinder with a charge amount Q due to electrostatic induction. The induced charge amount is measured by an electrometer (KEITHLEY6517A, manufactured by Keithley Instruments Co., Ltd.), and the ratio (Q / M) obtained by dividing the charge amount Q (mC) by the toner amount M (kg) in the inner cylinder is taken as the friction charge amount of the toner.
[0654] Triboelectric charge of toner (mC / kg) = Q / M
[0655] First, an evaluation image is formed on an electrostatic latent image bearing member, the rotation of the electrostatic latent image bearing member is stopped before the image is transferred to an intermediate transfer member, the toner on the electrostatic latent image bearing member is sucked and collected with a metal cylindrical pipe and a cylindrical filter, and [initial Q / M] is measured.
[0656] Subsequently, the developing device was left in an evaluation machine in an H / H environment for 2 weeks, and then the same operation as before storage was performed, and the charge amount Q / M (mC / kg) per unit mass on the electrostatic latent image bearing member after storage was measured. The initial Q / M per unit mass on the electrostatic latent image bearing member was taken as 100%, and the retention rate of Q / M per unit mass on the electrostatic latent image bearing member after storage was calculated and determined based on the following criteria ([Q / M after storage] / [initial Q / M]×100). In the case of evaluations A to D, it was determined that the effect of the present invention was obtained.
[0657] (Evaluation Criteria)
[0658] A: The retention rate is over 95%
[0659] B: The retention rate is 90% or more and less than 95%
[0660] C: The retention rate is 85% or more and less than 90%
[0661] D: The retention rate is 80% or more and less than 85%
[0662] E: Retention rate is less than 80%
[0663] <Examples 2 to 34 and Comparative Examples 1 to 10>
[0664] The evaluation was performed in the same manner as in Example 1 except that two-component developers 2 to 44 were used.
[0665] [Table 9]
[0666]
[0667] While the present invention has been described with reference to exemplary embodiments, it is to be understood that the invention is not limited to the disclosed exemplary embodiments. The scope of the following claims is to be accorded the broadest interpretation so as to encompass all such modifications and equivalent structures and functions.
Claims
1. A toner comprising toner particles containing a binder resin, characterized in that: The binder resin comprises a polymer A, The amount of the polymer A in the binder resin is 50.0% by mass or more, The polymer A is a polymer of the following composition: a first polymerizable monomer, and a second polymerizable monomer different from the first polymerizable monomer; The first polymerizable monomer is at least one monomer selected from the group consisting of (meth)acrylates having an alkyl group having 18 to 36 carbon atoms; The second polymerizable monomer is a compound represented by the following formula (A): In formula (A), X represents a single bond or an alkylene group having 1 to 6 carbon atoms, R 1 -C≡N, -C(=O)NHR 10 , or hydroxyl, where R 10 is a hydrogen atom or an alkyl group having 1 to 4 carbon atoms, R 3 is a hydrogen atom or a methyl group, Based on the total moles of all polymerizable monomers in the composition, the content of the first polymerizable monomer in the composition is 5.0 mol% to 60.0 mol%; Based on the total moles of all polymerizable monomers in the composition, the content of the second polymerizable monomer in the composition is 20.0 mol% to 95.0 mol%; The SP value of the first polymerizable monomer is determined by SP 12 (J / cm 3 ) 0.5 and the SP value of the second polymerizable monomer is represented by SP 22 (J / cm 3 ) 0.5 When , the following equations (4) and (5) are satisfied: The polymer A includes a multivalent metal; The multivalent metal is at least one metal selected from the group consisting of Mg, Ca, Al and Zn; and The content of the polyvalent metal in the toner particles is 25 ppm to 500 ppm by mass, 0.60≤(SP 22 -SP 12 )≤15.00(4), and 18.30 ≤ SP 22 (5), According to the calculation method proposed by Fedors, the evaporation energy Δei and molar volume Δvi of atoms or atomic groups in the molecular structure are determined, and (4.184×ΣΔei / ΣΔvi) 0.5 Taken as SP value (J / cm 3 ) 0.5 , where the unit of evaporation energy Δei is cal / mol and the unit of molar volume Δvi is cm 3 / mol. 2 . The toner according to claim 1 , wherein the content of the second polymerizable monomer in the composition is 40.0 mol % to 95.0 mol % based on the total moles of all polymerizable monomers in the composition.
3. The toner according to claim 1 or 2, wherein the content of the polyvalent metal in the toner particles and the content of the second polymerizable monomer in the composition satisfy the following formula (6), (The content of the polyvalent metal in the toner particles) / (The content of the second polymerizable monomer in the composition) ≥ 0.5 (ppm / mol%) (6). 4 . The toner according to claim 1 , wherein the first polymerizable monomer is at least one monomer selected from the group consisting of (meth)acrylates having a linear alkyl group having 18 to 36 carbon atoms.
5. The toner according to claim 1 or 2, wherein The polymer A includes a monovalent metal, and The monovalent metal is at least one metal selected from the group consisting of Na, Li, and K. 6 . The toner according to claim 5 , wherein the amount of the monovalent metal is 50% by mass to 90% by mass based on the total amount of the polyvalent metal and the monovalent metal. 7 . The toner according to claim 5 , wherein a domain diameter of at least one of the polyvalent metal and the monovalent metal in a cross section of the toner particle is from 10 nm to 50 nm.
8. The toner according to claim 1 or 2, wherein The complex elastic modulus at 65°C is 1.0×10 7 Pa to 5.0×10 7 Pa, and the complex elastic modulus at 85°C is 1.0×10 5 Below Pa.
9. A colorant according to claim 1 or 2, wherein in the concentration distribution of the polyvalent metal in the cross section of the colorant particle, the polyvalent metal concentration in the region from the surface of the colorant particle to a depth of 0.4 μm is lower than the polyvalent metal concentration in a region deeper than 0.4 μm from the surface of the colorant particle.
10. The toner according to claim 1 or 2, wherein The polymer A has a third monomer unit derived from a third polymerizable monomer, the third polymerizable monomer being different from the first polymerizable monomer and the second polymerizable monomer; and The third polymerizable monomer is at least one monomer selected from the group consisting of styrene, methyl methacrylate, and methyl acrylate.
11. A method for producing a toner, characterized in that: It includes: a step of preparing a resin fine particle dispersion liquid including a binder resin; a step of adding a flocculant to the resin fine particle dispersion to form aggregated particles; and a step of heating and fusing the aggregated particles to obtain a dispersion liquid including toner particles, wherein The binder resin comprises a polymer A, The amount of the polymer A in the binder resin is 50.0% by mass or more, The polymer A is a polymer of the following composition: a first polymerizable monomer, and a second polymerizable monomer different from the first polymerizable monomer; The first polymerizable monomer is at least one monomer selected from the group consisting of (meth)acrylates having an alkyl group having 18 to 36 carbon atoms; The second polymerizable monomer is a compound represented by the following formula (A): In formula (A), X represents a single bond or an alkylene group having 1 to 6 carbon atoms, R 1 -C≡N, -C(=O)NHR 10 , or hydroxyl, where R 10 is a hydrogen atom or an alkyl group having 1 to 4 carbon atoms, R 3 is a hydrogen atom or a methyl group, Based on the total moles of all polymerizable monomers in the composition, the content of the first polymerizable monomer in the composition is 5.0 mol% to 60.0 mol%; Based on the total moles of all polymerizable monomers in the composition, the content of the second polymerizable monomer in the composition is 20.0 mol% to 95.0 mol%; The SP value of the first polymerizable monomer is determined by SP 12 (J / cm 3 ) 0.5 and the SP value of the second polymerizable monomer is represented by SP 22 (J / cm 3 ) 0.5 When , the following equations (4) and (5) are satisfied: The flocculant includes a multivalent metal; The multivalent metal is at least one metal selected from the group consisting of Mg, Ca, Al and Zn; and The content of the polyvalent metal in the toner particles is 25 ppm to 500 ppm by mass, 0.60 ≤ (SP 22 - SP 12 ) ≤ 15.00(4), and 18.30 ≤ SP 22 (5), According to the calculation method proposed by Fedors, the evaporation energy Δei and molar volume Δvi of atoms or atomic groups in the molecular structure are determined, and (4.184×ΣΔei / ΣΔvi) 0.5 Taken as SP value (J / cm 3 ) 0.5 , where the unit of evaporation energy Δei is cal / mol and the unit of molar volume Δvi is cm 3 / mol. 12 . The method according to claim 11 , further comprising the step of adding a chelate compound having a chelate ability with respect to metal ions to the dispersion liquid including the toner particles.